Composition, composite film, membrane electrode assembly

A composition of perfluorocarbon and basic polymer fine particles addresses productivity and durability issues in electrolyte membranes, ensuring high chemical stability and conductivity under demanding conditions.

JP7607411B2Active Publication Date: 2024-12-27ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 30 Cites 0 Cited by

Patent Information

Application Number
JP2020093875
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-08-08
Filing Date
2020-05-29
Publication Date
2024-12-27
Estimated Expiration
2038-02-22

AI Technical Summary

Technical Problem

Existing methods for producing electrolyte membranes in fuel cells face challenges such as low solid content concentration, poor productivity, solvent decomposition, and difficulty in achieving high chemical durability, especially under harsh conditions like high temperatures and low humidity.

Method used

A composition comprising 100 parts by mass of a perfluorocarbon polymer with ion exchange groups and 0.1 to 200 parts by mass of a basic polymer, where the basic polymer is in fine particle form with a concentration of basic groups per gram of 5.0 mmol or less, enhances dispersibility and chemical durability.

Benefits of technology

The composition results in a highly viscous mixture that facilitates the production of electrolyte membranes with excellent chemical durability and ion conductivity, even under high temperature and low humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607411000047
    Figure 0007607411000047
  • Figure 0007607411000048
    Figure 0007607411000048
  • Figure 0007607411000049
    Figure 0007607411000049
Patent Text Reader

Abstract

To provide a composition that has excellent productivity when producing an electrolyte membrane and that is capable of imparting excellent chemical durability to the electrolyte membrane to be obtained, as well as an electrolyte membrane and a membrane electrode assembly containing the composition.SOLUTION: The present invention provides a composition comprising 100.0 pts.mass of a perfluorocarbon polymer having an ion-exchange group (A) and 0.1 to 200.0 pts.mass of a basic polymer (B), and a composition comprising a polyimide having a structure represented by formula (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a composite membrane, and a membrane electrode assembly. [Background technology]

[0002] Fuel cells are power generation devices that generate electrical energy by electrochemically oxidizing fuels such as hydrogen and methanol, and have been attracting attention as a clean energy supply source. In particular, solid polymer electrolyte fuel cells operate at lower temperatures than other types of fuel cells, and are therefore used as power sources for automobile alternative power sources, home cogeneration systems, portable generators, etc. It is known that in the presence of fuel and catalyst used in the cell reaction of solid polymer electrolyte fuel cells, peroxides are generated and turn into radicals in the diffusion process, which deteriorate the electrolyte membrane. Therefore, in order to use fuel cells for a long period of time, it is necessary to give the electrolyte membrane high chemical durability.

[0003] Fluorine-based resins are generally known to have higher radical resistance than hydrocarbon-based resins, and fluorine-based polymer electrolytes having perfluorocarbon main chains and sulfonic acid groups in the side chains are widely used for solid polymer electrolyte membranes. However, as fuel cells become more widely used, there is a demand for even higher durability. As a method for improving chemical durability, a method of adding a basic polymer to the electrolyte membrane has been investigated. For example, Patent Document 1 discloses a technique in which a polyazole compound is dissolved in an aprotic solvent and added to a fluorine-based polymer electrolyte. Patent Document 2 discloses a technique in which a polyazole compound is dissolved in an alkali metal hydroxide and the resulting solution is added to a fluorine-based polymer electrolyte. Patent Document 3 discloses a technique in which a polyazole compound is added in the form of particles to a hydrocarbon-based polymer electrolyte. Patent Document 4 discloses a technique in which a solution in which a polyazole compound is dissolved in an aprotic solvent and a solution in which a polyimide precursor is dissolved in an aprotic solvent are added to a fluorine-based polymer electrolyte.

[0004] Moreover, the solid polymer electrolyte fuel cell at least includes a membrane electrode assembly in which gas diffusion electrodes, each of which is a stack of an electrode catalyst layer and a gas diffusion layer, are bonded to both sides of a proton exchange membrane. The proton exchange membrane referred to here is a material that has strong acidic groups, such as sulfonic acid groups and carboxylic acid groups, in the polymer chain and has the property of selectively permeating protons. As such a proton exchange membrane, a perfluoro-based proton exchange membrane, such as Nafion (registered trademark, manufactured by DuPont), which has high chemical stability, is preferably used.

[0005] During fuel cell operation, fuel (e.g., hydrogen) is supplied to the gas diffusion electrode on the anode side, and an oxidant (e.g., oxygen or air) is supplied to the gas diffusion electrode on the cathode side, and the two electrodes are connected by an external circuit to operate the fuel cell. Specifically, when hydrogen is used as fuel, it is oxidized on the anode catalyst to produce protons. These protons pass through the proton-conducting polymer in the anode catalyst layer, then move through the proton exchange membrane, pass through the proton-conducting polymer in the cathode catalyst layer, and reach the cathode catalyst. On the other hand, the electrons generated simultaneously with the protons by the oxidation of hydrogen pass through an external circuit and reach the cathode gas diffusion electrode. On the cathode catalyst, the protons react with oxygen in the oxidant to produce water. At this time, electrical energy is extracted. In this case, the proton exchange membrane must also function as a gas barrier wall. If the proton exchange membrane has a high gas permeability, hydrogen on the anode side leaks to the cathode side and oxygen on the cathode side leaks to the anode side, i.e., cross leakage occurs, resulting in a so-called chemical short state and making it impossible to obtain a satisfactory voltage.

[0006] Such solid polymer electrolyte fuel cells are usually operated at around 80°C to obtain high output characteristics. In particular, when used for automobile applications, it is desired that the fuel cell can be operated under high temperature and low humidity conditions, assuming that the automobile will be driven in the summer. From this perspective, Patent Document 5 proposes a polymer electrolyte composition containing a polymer electrolyte, a compound having a thioether group, and a compound having an azole ring, and it is said that the use of the composition will result in high chemical stability. Patent Document 6 proposes an electrolyte membrane comprising a proton-conducting polymer using a nanofiber mat as a core material, and it is said that the electrolyte membrane is thermally and chemically robust and exhibits excellent dimensional stability during the operation of the fuel cell in a harsh environment at high temperatures. In addition, Patent Document 7 proposes a method for producing a proton exchange membrane using a crosslinked porous membrane. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-084278 A [Patent Document 2] JP 2015-219941 A [Patent Document 3] JP 2013-080701 A [Patent Document 4] JP Patent Publication No. 2005-336475 [Patent Document 5] Patent No. 5548445 specification [Patent Document 6] Patent No. 5798186 specification [Patent Document 7] Chinese Patent No. 104629081 Summary of the Invention [Problem to be solved by the invention]

[0008] <First Object of the Invention> In the production of an electrolyte membrane, a method of producing the membrane using a solution in which a basic polymer is dissolved in a solvent is widely used. However, it is difficult to prepare a stable solution using a basic polymer, and even if an aprotic solvent in which the basic polymer is soluble is used, there is a problem that the polymer cannot be dissolved at a high concentration. The composition containing the polyazole compound disclosed in Patent Document 1 has a low solid content concentration, and in order to obtain a film of a desired thickness using the composition, it is necessary to repeat coating and drying multiple times, which results in poor productivity. Furthermore, aprotic solvents capable of dissolving basic polymers have high boiling points, and when the solvent is removed to increase the viscosity, high temperatures are required, which results in decomposition of the basic polymer due to its coexistence with the strong acid contained in the electrolyte, as well as decomposition and denaturation of the electrolyte itself. Patent Document 2 discloses a method for dissolving a basic polymer using an alkali metal hydroxide. However, this method requires a step for removing ions derived from the alkali metal hydroxide, which results in poor productivity. Patent Document 3 discloses a method of adding polyazole compound particles to a hydrocarbon-based electrolyte. However, when basic polymer particles are added to a fluorine-based polymer electrolyte, the particles aggregate, making it difficult to stably produce a homogeneous membrane. Patent Document 4 also does not recognize the above problem, and has the same problem as Patent Document 1.

[0009] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and a first object of the present invention is to provide a composition which is excellent in productivity when producing an electrolyte membrane and which can impart excellent chemical durability to the obtained electrolyte membrane, as well as an electrolyte membrane and a membrane electrode assembly which contain the same.

[0010] <Second Object of the Invention> The polymer electrolyte composition described in Patent Document 5 is said to exhibit sufficient durability under high-temperature, low-humidity conditions at an operating temperature of about 100° C. and a humidity of about 12 RH%, but there is still room for improvement in the electrolyte from the viewpoint of durability under more severe conditions (for example, an operating temperature of about 120° C.). Regarding the electrolyte membrane described in Patent Document 6, there is still room for improvement when considering use under the harsh conditions described above, particularly in terms of membrane resistance (ionic conductivity) and embeddability of the core material in the electrolyte. Furthermore, Patent Document 7 describes that a proton exchange membrane with high tensile strength can be obtained by crosslinking a porous membrane, but there is room for improvement in terms of durability.

[0011] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and has a second object to provide a composition that can exhibit excellent embeddability due to good affinity between an electrolyte and a core material, and that exhibits excellent durability and ionic conductivity even under high temperature and low humidity conditions, as well as a composite membrane, a membrane electrode assembly, a fuel cell, and a fuel cell system each using the same. [Means for solving the problem]

[0012] <Means for solving the first problem> Means of Solving the Problem The present inventors have conducted extensive research to solve the first problem, and as a result have found that a composition having a specific configuration can solve the problem, thereby completing the present invention.

[0013] <Means for solving the second problem> As a result of intensive research into solving the second problem, the present inventors have found that a composition containing a polyimide having a specific structure can solve the above problem, and have thus completed the present invention.

[0014] That is, the present invention is as follows. The first problem described above can be solved by the following first group of inventions, and the second problem described above can be solved by the following second group of inventions.

[0015] <First group of inventions> [1] (A) 100.0 parts by mass of a perfluorocarbon polymer having an ion exchange group; (B) 0.1 to 200.0 parts by mass of a basic polymer, The composition, wherein the (B) basic polymer is in the form of fine particles. [2] (A) 100.0 parts by mass of a perfluorocarbon polymer having an ion exchange group; (B) 0.1 to 200.0 parts by mass of a basic polymer, The composition (B) has a basic group concentration per 1 g of the basic polymer of 5.0 mmol or less. [3] The composition according to [2], wherein the concentration of basic groups per 1 g of the basic polymer (B) is 3.0 mmol or less. [4] the (B) basic polymer is in the form of fine particles, The composition according to any one of [1] to [3], wherein the proportion of fine particles having a particle size of more than 5.0 μm among the fine particles of the basic polymer (B) is 10% or less. [5] the (B) basic polymer is in the form of fine particles, The composition according to any one of [1] to [4], wherein the average diameter of the fine particles of the basic polymer (B) is 0.10 μm or more and 5.00 μm or less. [6] The composition according to any one of [1] to [5], wherein the (B) basic polymer contains an imide and / or amide structure. [7] The composition according to any one of [1] to [6], comprising 0.1 parts by mass or more and 20.0 parts by mass or less of the basic polymer (B) relative to 100.0 parts by mass of the perfluorocarbon polymer (A) having an ion exchange group. [8] The composition according to any one of [1] to [7], wherein the (B) basic polymer has an azole ring. [9] The composition according to any one of [1] to [8], wherein the (B) basic polymer has two or more azole rings, and an imide and / or amide structure located between the two or more azole rings.

[10] The composition according to any one of [1] to [9], wherein the weight average molecular weight (Mw) of the (B) basic polymer is 300 or more and 500,000 or less.

[11] The composition according to any one of [1] to

[10] , wherein the molecular weight distribution of the (B) basic polymer, calculated as weight average molecular weight (Mw) / number average molecular weight (Mn), is 2.60 or less.

[12] The composition according to any one of [1] to

[11] , wherein the (B) basic polymer contains one or more structures selected from the group consisting of an imidazole ring, a benzimidazole ring, an oxazole ring, a benzoxazole ring, a thiazole ring, and a benzothiazole ring.

[13] The composition according to any one of [1] to

[12] , wherein the (B) basic polymer has a structure represented by formula (1). [ka] (In formula (1), Y represents a tetravalent organic group.)

[14] The composition according to any one of [1] to

[13] , wherein the ion exchange capacity of the (A) perfluorocarbon polymer having an ion exchange group is 0.5 to 3.0 milliequivalents / g.

[15] The composition according to any one of [1] to

[14] , wherein the (A) perfluorocarbon polymer having an ion exchange group is a perfluorocarbon polymer having a structure represented by formula (2). -[CF2CX 1 X 2 ] a -[CF2-CF((-O-CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 )] g - (2) (In formula (2), X 1 , X 2 and X3 is independently selected from the group consisting of a halogen atom and a perfluoroalkyl group having 1 to 3 carbon atoms. X 4 represents COOZ, SO3Z, PO3Z2, or PO3HZ. Z is a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, or NH4, NH3R x1 , NH2R x1 R x2 , NHR x1 R x2 R x3 , NR x1 R x2 R x3 R x4 represents amines selected from the group consisting of. R x1 , R x2 , R x3 , and R x4 each independently represents an alkyl group or an arene group. Here, when X 4 is PO3Z2, Z may be the same or different. R 1 and R 2 each independently represents a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, or a fluorochloroalkyl group. a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e, and f are each independently integers from 0 to 6 (provided that d, e, and f are not simultaneously 0).)

[16] The composition according to any one of [1] to

[15] , wherein the perfluorocarbon polymer having the (A) ion-exchange group has a structure represented by the formula (4). -[CF2CF2] a -[CF2-CF((-O-(CF2) m -X 4 )] g - (4) (In formula (4), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, m is an integer from 1 to 6, and X 4 represents SO3H.)

[17] An electrolyte membrane comprising the composition according to any one of [1] to

[16] .

[18] The electrolyte membrane according to

[17] , wherein the basic polymer (B) contained in the electrolyte membrane is fine particles, the coefficient of variation of the particle diameter of the basic polymer (B) contained in a region of 62.8 μm × 26.0 μm in the SEM image of the membrane cross-section of the electrolyte membrane is 0.10 or more and 2.00 or less.

[19] The electrolyte membrane according to

[18] , wherein the coefficient of variation of the particle diameter of the basic polymer (B) is 0.20 or more and 1.50 or less.

[20] A membrane electrode assembly comprising the electrolyte membrane according to any one of

[17] to

[19] .

[21] The electrolyte membrane according to any one of

[17] to

[19] , and a membrane containing polyimide, and is a composite membrane comprising: The composite membrane, wherein the polyimide has a structure represented by formula (1).

Chemical formula

[22] The composite membrane according to

[21] , wherein the membrane containing polyimide is in the form of a fiber sheet.

[0016] <Second group of inventions>

[23] A composition comprising a polyimide having a structure represented by formula (1).

Chemical formula

[24] The composition according to

[23] , comprising a polyimide having a structure represented by formula (5). [ka] (In formula (5), Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:30.) [twenty five] The composition according to

[23] , comprising a polyimide having a structure represented by formula (6). [ka] (In formula (6), Y represents a tetravalent organic group, k and l represent the numbers of repeating units, and the ratio of k:l is 20:80 to 70:30.)

[26] The composition according to

[23] or

[24] , wherein Y is represented by formula (Y1): [ka]

[27] The composition according to any one of

[23] to

[25] , wherein the Y is a tetravalent organic group having an alicyclic structure.

[28] The composition according to any one of

[23] to

[27] , having a molecular weight distribution calculated by Mw / Mn of 2.60 or less.

[29] The composition according to any one of

[23] to

[28] , which, when made into a porous body or a fiber sheet, experiences a weight loss of 10 mass% or less at 30°C to 350°C in a nitrogen atmosphere.

[30] A porous body produced from the composition according to any one of

[23] to

[29] .

[31] A fiber sheet produced from the composition according to any one of

[23] to

[29] .

[32] A fiber sheet comprising a polyimide represented by formula (7). [ka] (In formula (7), A is a divalent organic group represented by formula (A-1), (A-2), (A-3) or (A-4); [ka] (In the above formulas (A-1), (A-3), and (A-4), X1 is a divalent organic group represented by the following formula (X1-1) or (X1-2); [ka] In formulae (A-2) and (A-3), L represents a methyl group or a trifluoromethyl group, and in formula (A-4), R represents a hydroxyl group. Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:30.

[33] A fiber sheet comprising a polyimide represented by formula (8). [ka] (In formula (8), D and Y represent tetravalent organic groups, and the ratio of k:l is 20:80 to 70:30.)

[34] The fiber sheet according to

[33] , wherein D is a tetravalent organic group represented by formula (D1). [ka] (In formula (D1), X1 is a divalent organic group represented by formula (X1-1) or (X1-2); [ka] Represents.)

[35] The fiber sheet according to any one of

[32] to

[34] , wherein the average fiber diameter is 100 nm or more and 1000 nm or less.

[36] A composite membrane comprising the fiber sheet according to any one of

[31] to

[35] and an electrolyte having proton conductivity, wherein the electrolyte having proton conductivity is present in the fiber sheet.

[37] The composite membrane according to

[36] , wherein the proton-conductive electrolyte is a perfluorocarbon polymer having an ion-exchange group.

[38] A membrane electrode assembly comprising the composite membrane according to

[37] .

[39] A fuel cell comprising the membrane electrode assembly according to

[38] .

[40]

[39] A fuel cell system comprising the fuel cell according to the present invention. Effect of the Invention

[0017] <Effects of the First Embodiment> According to the composition of the present invention, a highly viscous composition having good dispersibility can be obtained, and excellent chemical durability can be imparted to the resulting electrolyte membrane.

[0018] <Effects of the Second Embodiment> According to the composition of the present invention, a composite membrane with excellent embeddability due to the good affinity between the electrolyte and the core material can be provided, and the composition can exhibit excellent durability and ionic conductivity even under high temperature and low humidity conditions. [Brief description of the drawings]

[0019] [Figure 1] 1 shows an SEM photograph of a cross section of the electrolyte membrane obtained in Example A1. [Diagram 2] 1 shows an SEM photograph of the core material (porous body) obtained in Example B1. [Diagram 3] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Example B1. [Figure 4] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Comparative Example B1. [Diagram 5] 1 shows an SEM photograph of the core material (fiber sheet) obtained in Example C1. [Figure 6] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Example C1. [Figure 7] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Comparative Example C1. [Figure 8] 1 shows an SEM photograph of the core material (porous body) obtained in Example D1. [Figure 9] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Example D1. [Figure 10] 1 shows an SEM photograph of a cross section of the composite membrane obtained in Comparative Example D1. [Figure 11] The cross section of the electrolyte membrane in the thickness direction was photographed with a 2000x scanning electron microscope (SEM), and an image of an area of ​​62.8 μm × 26.0 μm is shown. [Figure 12] The image was binarized using the Triangle method using the image processing software ImageJ 1.50i. [Figure 13] The image was taken using the image processing software ImageJ 1.50i, and binarized using the Triangle method. The particle portion was then analyzed and extracted using Analyze Particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The present invention is not limited to the following description, and can be modified in various ways within the scope of the present invention. The first embodiment of the invention will be referred to as the "first embodiment" below, and the second embodiment of the invention will be referred to as the "second embodiment" below.

[0021] <<First embodiment>> <Composition> The composition of the present embodiment contains 0.1 parts by mass or more of (B) basic polymer (hereinafter also simply referred to as "B component"), preferably 1.0 parts by mass or more, and more preferably 1.5 parts by mass or more, per 100.0 parts by mass of (A) perfluorocarbon polymer having an ion exchange group (hereinafter also simply referred to as "A component"). By containing 0.1 parts by mass or more of (B) basic polymer, the electrolyte membrane obtained from the composition has excellent chemical durability. In addition, the basic polymer (B) is contained in an amount of 200.0 parts by mass or less, preferably 30.0 parts by mass or less, more preferably 20.0 parts by mass or less, and even more preferably 15.0 parts by mass or less, per 100.0 parts by mass of the perfluorocarbon polymer having an ion exchange group. By containing 200.0 parts by mass or less of (B) basic polymer, the electrolyte membrane obtained from the composition has excellent conductivity. That is, the composition of the present embodiment contains (A) 100.0 parts by mass of a perfluorocarbon polymer having an ion exchange group, and (B) 0.1 to 200.0 parts by mass of a basic polymer. The (B) basic polymer contained in the composition of the present embodiment is preferably contained in an amount of 0.1 to 20.0 parts by mass relative to 100.0 parts by mass of the (A) perfluorocarbon polymer having an ion exchange group.

[0022] The (B) basic polymer in this embodiment satisfies the following requirements: the (B) basic polymer is in the form of fine particles, and / or the (B) basic polymer has a basic group concentration of 5.0 mmol or less per 1 g of the (B) basic polymer. That is, one of the present embodiments is a composition comprising (A) 100.0 parts by mass of a perfluorocarbon polymer having an ion exchange group and (B) 0.1 to 200.0 parts by mass of a basic polymer, the basic polymer (B) being in the form of fine particles. Also, one of the present embodiments is a composition comprising (A) 100.0 parts by mass of a perfluorocarbon polymer having an ion exchange group, and (B) 0.1 to 200.0 parts by mass of a basic polymer, in which the concentration of the basic group per 1 g of the basic polymer (B) is 5.0 mmol or less. The composition of the present embodiment is a highly viscous composition with favorable dispersibility that is advantageous when producing an electrolyte membrane, and can impart excellent chemical durability to an electrolyte membrane obtained from the composition. The electrolyte membrane obtained from the composition of the present embodiment can be suitably used for a solid polymer electrolyte membrane, a membrane electrode assembly, and a solid polymer electrolyte fuel cell.

[0023] (Component A: Perfluorocarbon polymer having ion exchange groups) The perfluorocarbon polymer having an ion exchange group (A) in this embodiment is not particularly limited, but representative examples include perfluorocarbon polymers having an ion exchange group represented by formula (2), such as Nafion (registered trademark: manufactured by DuPont, USA), Aciplex (registered trademark: manufactured by Asahi Kasei Corporation, Japan), and Flemion (registered trademark: manufactured by Asahi Glass Co., Ltd., Japan). A perfluorocarbon polymer having an ion exchange group is a polymer electrolyte having a fluorine atom in at least one repeating unit. Specific examples thereof include, but are not limited to, perfluorocarbon polymer compounds having a structural unit represented by formula (2).

[0024] -[CF2CX 1 X 2 ] a -[CF2-CF((-O-CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF) f -X 4 )] g - (2)

[0025] In formula (2), X 1 , X 2 and X 3 are each independently selected from the group consisting of a halogen atom and a perfluoroalkyl group having 1 to 3 carbon atoms. The halogen atom is not particularly limited, but includes a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, and is preferably a fluorine atom or a chlorine atom. X 4 represents COOZ, SO3Z, PO3Z2, or PO3HZ. Z is a hydrogen atom, an alkali metal atom such as a lithium atom, a sodium atom, or a potassium atom; an alkaline earth metal atom such as a calcium atom or a magnesium atom; or NH4, NH3R x1 , NH2R x1 R x2 , N.H.R. x1 R x2 R x3 , N.R. x1 R x2 R x3 R x4 R is an amine selected from the group consisting of x1 , R x2 , R x3 , and R x4 each independently represents an alkyl group or an arene group. The arene group is not particularly limited, but examples thereof include residues in which one hydrogen atom has been removed from the nucleus of an aromatic hydrocarbon (a monocyclic or fused ring having 6 to 16 carbon atoms), and specific examples thereof include a phenyl group, a tolyl group, and a naphthyl group. The alkyl and arene groups may be substituted. X 4 When is PO3Z2, Z may be the same or different. R x1 , R x2 , R x3 , and R x4 The alkyl group in the formula (I) is not particularly limited, and may be any of the following: n H 2n+1 (n is an integer of 1 or more, preferably an integer of 1 to 20, and more preferably an integer of 1 to 10). x1 , R x2 , R x3 , and R x4Specific examples of the alkyl group in [compound name] include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, and the like. R 1 and R 2 each independently represent a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, or a fluorochloroalkyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom or a chlorine atom is preferred. a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e, and f are each independently integers from 0 to 6 (however, d, e, and f are not simultaneously 0).

[0026] When Z in formula (2) is an alkaline earth metal, for example, two Xs may form a salt with the alkaline earth metal, such as (COO)2Z or (SO3)2Z. 4 may form a salt with the alkaline earth metal.

[0027] Among the perfluorocarbon polymers having an ion exchange group, a perfluorocarbon sulfonic acid polymer represented by formula (3) or (4) or a metal salt thereof is more preferred. -[CF2CF2] a -[CF2-CF((-O-CF2-CF(CF3)) b -O-(CF2) h -SO3X)] g - (3)

[0028] In formula (3), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, b is an integer from 1 to 3, h is an integer from 1 to 8, and X is a hydrogen atom or an alkali metal atom.

[0029] -[CF2CF2] a -[CF2-CF((-O-(CF2) m -X 4 )] g - (4)

[0030] In formula (4), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, m is an integer from 1 to 6, and X 4 represents SO3H.

[0031] The perfluorocarbon polymer having an ion exchange group that can be used in this embodiment can be produced, for example, by polymerizing a precursor polymer represented by formula (I) and then performing alkali hydrolysis, acid treatment, etc. -[CF2CX 1 X 2 a -[CF2-CF((-O-CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 5 )] g - (I)

[0032] In formula (I), X 1 , X 2 and X 3 are each independently selected from the group consisting of a halogen atom and a perfluoroalkyl group having 1 to 3 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom or a chlorine atom is preferred. X 5 is COOR 3 , COR 4 or SO2R 4 . R 3 is a hydrocarbon-based alkyl group having 1 to 3 carbon atoms. R 4 is a halogen atom. R 1 and R 2 ​Each is independently selected from the group consisting of a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, and a fluorochloroalkyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom or a chlorine atom is preferable. a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e, and f are each independently an integer from 0 to 6. However, d, e, and f are not simultaneously 0.

[0033] The precursor polymer represented by formula (I) can be produced, for example, by copolymerizing an olefin fluoride compound and a vinyl fluoride compound.

[0034] Here, the olefin fluoride compound is not particularly limited, and examples thereof include a compound represented by formula (1a).

[0035] CF2=CX 1 X 2 (1a) In formula (1a), X 1 and X 2 are synonymous with X 1 and X 2 in formula (I).

[0036] Specific examples of the compound represented by formula (1a) include CF2=CF2, CF2=CFCl, CF2=CCl2, etc.

[0037] In addition, the vinyl fluoride compound is not particularly limited, and examples thereof include a compound represented by formula (1b).

[0038] CF2=CF((-O-CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 )e -(CF2) f -X 5 ) (1b) In formula (1b), X 3 , X 5 , R 1 , R 2 , b, c, d, e and f are X in formula (I). 3 , X 5 , R 1 , R 2 , b, c, d, e and f.

[0039] Specific examples of the compound represented by formula (1b) include CF2=CF(-O-(CF2) j -SO2F), CF2=CF(-O-CF2CF(CF3)-O-(CF2) j -SO2F), CF2=CF((-O-CF2CF(CF3)) j -(CF2) j-1 -SO2F), CF2=CF(-O-(CF2) j -CO2R), CF2=CF(-O-CF2CF(CF3)-O-(CF2) j -CO2R), CF2=CF(-(CF2) j -CO2R), CF2=CF((-OCF2CF(CF3)) j -(CF2)2-CO2R) (wherein j is an integer of 1 to 8, and R is a hydrocarbon alkyl group having 1 to 3 carbon atoms).

[0040] The precursor polymer as described above can be synthesized by a known method. The synthesis method is not particularly limited, but examples thereof include the following methods. (i) Solution polymerization: a method in which a polymerization solvent such as a fluorinated hydrocarbon is used, and a vinyl fluoride compound and a fluorinated olefin gas are reacted with each other while the compound is filled and dissolved in the polymerization solvent to carry out polymerization. The fluorine-containing hydrocarbon is not particularly limited, but for example, the group of compounds collectively known as "fluorocarbons", such as trichlorotrifluoroethane and 1,1,1,2,3,4,4,5,5,5-decafluoropentane, can be suitably used. (ii) Bulk polymerization: a method in which the polymerization of a vinyl fluoride compound is carried out using the vinyl fluoride compound itself as a polymerization solvent without using a solvent such as a fluorinated hydrocarbon. (iii) Emulsion polymerization: a method in which an aqueous solution of a surfactant is used as a polymerization solvent, and a vinyl fluoride compound and a fluorinated olefin gas are reacted in a state of being filled and dissolved in the polymerization solvent to carry out polymerization. (iv) Miniemulsion polymerization and microemulsion polymerization: a method in which an aqueous solution of an interfacial polymerization agent and an emulsifier such as alcohol is used, and a vinyl fluoride compound and a fluorinated olefin gas are reacted with each other in an emulsified state in the aqueous solution to carry out polymerization. (v) Suspension polymerization: a method in which an aqueous solution of a suspension stabilizer is used, and a vinyl fluoride compound is reacted with a fluorinated olefin gas while the compound is suspended in the aqueous solution to carry out polymerization.

[0041] In this embodiment, the melt mass flow rate (hereinafter sometimes abbreviated as "MFR") can be used as an index of the polymerization degree of the precursor polymer. In the present embodiment, from the viewpoint of facilitating molding, the MFR of the precursor polymer is preferably 0.01 or more, more preferably 0.1 or more, and even more preferably 0.3 or more. The upper limit of the MFR is not particularly limited, but from the viewpoint of facilitating molding, it is preferably 100 or less, more preferably 50 or less, and even more preferably 10 or less.

[0042] The precursor polymer prepared as described above is hydrolyzed in a basic reaction liquid, thoroughly washed with warm water, and then acid-treated. Through this hydrolysis and acid treatment, for example, the perfluorocarbon sulfonic acid resin precursor is protonated to become a perfluorocarbon sulfonic acid resin in the form of SO3H.

[0043] The perfluorocarbon polymer having an ion exchange group (A) in this embodiment preferably has an ion exchange capacity of 0.5 to 3.0 milliequivalents / g, and preferably has an ion exchange group to satisfy this condition. By making the ion exchange capacity 3.0 milliequivalents / g or less, the swelling of the polymer electrolyte membrane containing this polymer electrolyte under high temperature and high humidity during fuel cell operation tends to be reduced. Reducing the swelling of the polymer electrolyte membrane can improve problems such as a decrease in the strength of the polymer electrolyte membrane, the occurrence of wrinkles that cause peeling from the electrode, and further the problem of a decrease in gas barrier properties. On the other hand, by making the ion exchange capacity 0.5 milliequivalents / g or more, a fuel cell equipped with a polymer electrolyte membrane that satisfies such conditions can maintain its power generation capacity well. From these viewpoints, the ion exchange capacity of the perfluorocarbon polymer having an ion exchange group (component A) is more preferably 0.6 to 2.8 milliequivalents / g, and even more preferably 1.3 to 2.5 milliequivalents / g.

[0044] The ion exchange capacity of the perfluorocarbon polymer having an ion exchange group in this embodiment is measured as follows. First, a membrane made of a polymer electrolyte in which the counter ions of the ion exchange groups are in the state of protons is immersed in a saturated NaCl aqueous solution at 25°C, and the aqueous solution is stirred for a sufficient time. Next, the protons in the saturated NaCl aqueous solution are neutralized by titration with a 0.01N aqueous sodium hydroxide solution. The membrane made of a polymer electrolyte in which the counter ions of the ion exchange groups are in the state of sodium ions obtained by filtration after neutralization is rinsed with pure water, further vacuum dried, and then weighed. The amount of sodium hydroxide required for neutralization is M (mmol), and the mass of the membrane made of a polymer electrolyte in which the counter ions of the ion exchange groups are sodium ions is W (mg), and the equivalent mass EW (g / equivalent) is calculated by the following formula. EW=(W / M)-22

[0045] (Component B: Basic polymer) The basic polymer (B) in this embodiment is a polymer containing a basic group. The basic polymer (B) in this embodiment satisfies the following requirements: the polymer is in the form of fine particles, and / or the concentration of the basic group per gram of the basic polymer (B) is 5.0 mmol or less. The basic polymer (B) in this embodiment is preferably a polymer containing at least one structure derived from a nitrogen-containing aliphatic compound and / or a nitrogen-containing aromatic compound as a structure that imparts basicity, and more preferably a polymer containing an imide and / or amide structure. The basic polymer (B) in this embodiment is preferably a polymer containing a structure derived from an aromatic imide, from the viewpoint of heat resistance and chemical durability when formed into an electrolyte membrane.

[0046] The structure that imparts basicity is preferably contained in the main chain and / or side chain of the polymer. As the structure that imparts basicity, from the viewpoint of heat resistance, a structure derived from a nitrogen-containing aromatic compound is preferable, and examples of such nitrogen-containing aromatic compounds include, but are not limited to, structures derived from aniline, pyrrole, imidazole, pyrazole, triazole, tetrazole, isoindole, indole, benzimidazole, indazole, benzotriazole, imidazopyridine, imidazopyrimidine, pyrazolopyrimidine, triazolopyrimidine, oxazole, benzoxazole, thiazole, benzothiazole, and isothiazole. The basic polymer (B) preferably contains an azole ring structure. The basic polymer (B) preferably contains one or more structures selected from the group consisting of an imidazole ring, a benzimidazole ring, an oxazole ring, a benzoxazole ring, a thiazole ring, and a benzothiazole ring, more preferably contains an imidazole structure, and further preferably contains a benzimidazole structure.

[0047] From the viewpoint of dispersibility when a composition is formed with the perfluorocarbon polymer (A) having an ion exchange group, the basic polymer (B) contained in the composition of the present embodiment has a concentration of basic groups per 1 g of the basic polymer (B) of preferably 5.0 mmol or less, more preferably 3.0 mmol or less, and even more preferably 2.5 mmol or less. From the viewpoint of the chemical durability of an electrolyte membrane obtained from the composition, the concentration of the basic groups is preferably 0.01 mmol or more, more preferably 0.03 mmol or more, and even more preferably 0.05 mmol or more. If the concentration of basic groups is high, when a composition is formed with the perfluorocarbon polymer (A) having an ion exchange group, aggregation due to interaction between particles is likely to occur. Therefore, the surface area of ​​the basic polymer particles is reduced, making it difficult to capture radicals generated in the surroundings. If it becomes difficult to capture radicals, there is a risk that the electrolyte membrane will be deteriorated by the radicals, so the concentration of basic groups is preferably 5.0 mmol or less. In addition, the (B) basic polymer may be microparticulated as necessary, and from the viewpoint of facilitating pulverization for the microparticulation, it is preferable that the (B) basic polymer contains an imide and / or amide structure at any position. The imide and / or amide structure is included in the main chain structure of the (B) basic polymer, and the imide and / or amide structure is included between structures that impart basicity, which tends to keep the concentration of basic groups per gram of the basic polymer low. The concentration of basic groups per gram of the (B) basic polymer can be measured by a known measurement method such as NMR. When measuring the basic polymer contained in the electrolyte membrane, the (A) perfluorocarbon polymer having an ion exchange group in the electrolyte membrane is dissolved using hot water or a fluorine-based solvent, and the (B) basic polymer is separated by a known method such as centrifugation or pressure filtration, and then the concentration can be measured by NMR.

[0048] The basic polymer (B) can be synthesized by using known synthesis methods alone or in combination. Examples of the method for producing the basic polymer (B) include the following methods. (a) A method of reacting a diamine having an azole ring structure with a tetracarboxylic dianhydride. (b) A method of reacting a diamine having an azole ring structure with a dicarboxylic acid chloride. (c) A method in which a diamine having an azole ring structure is subjected to a dehydration condensation reaction with a dicarboxylic acid. (d) A method of subjecting a dicarboxylic acid having an azole ring structure to a dehydration condensation reaction with a diamine. (e) A method in which a dicarboxylic acid having an azole ring structure is converted into a diacid chloride, and then reacted with a diamine. (f) A method of reacting a compound having an azole ring structure and further having an amino group and a hydroxy group with a tetracarboxylic dianhydride. (g) A method in which a tetraamine is reacted with a dicarboxylic acid to form an oligomer having an azole ring structure, and then the reaction is further carried out using any of the reactions (a) to (f). (h) A method of reacting a compound having a monofunctional azole ring with the terminal of a polymer having an imide and / or amide structure. (i) A method in which a compound having a monofunctional azole ring is reacted with a polymer having an imide and / or amide structure to form a side chain. Compounds that can be used in the above reactions (a) to (i) are explained below. These are not limited to being used alone, and two or more of them may be used in combination in the reaction.

[0049] The bifunctional compound having an azole ring structure, i.e., a diamine having an azole ring structure, a dicarboxylic acid having an azole ring structure, and a compound having an azole ring structure and further having an amino group and a hydroxy group, are not particularly limited, and examples thereof include 5-amino-2-mercaptobenzimidazole, 6-amino-2-mercaptobenzimidazole, 2-amino-4-hydroxybenzimidazole, 2-(4-carboxyphenyl)-5-carboxybenzimidazole, 5-amino-2-(4-aminophenyl)benzimidazole, 5-amino-2-mercapto ... Examples of mercaptobenzothiazole include 6-amino-2-mercaptobenzothiazole, 2-amino-4-hydroxybenzothiazole, 2-(4-carboxyphenyl)-5-carboxybenzothiazole, 5-amino-2-(4-aminophenyl)benzothiazole, 5-amino-2-mercaptobenzoxazole, 6-amino-2-mercaptobenzoxazole, 2-amino-4-hydroxybenzoxazole, 2-(4-carboxyphenyl)-5-carboxybenzoxazole, and 5-amino-2-(4-aminophenyl)benzoxazole. The compound having a bifunctional azole ring structure may further have a substituent.

[0050] The compound having a monofunctional azole ring is not particularly limited, but examples thereof include 2-aminobenzimidazole, 2-mercaptobenzimidazole, 2-hydroxybenzimidazole, 5-aminobenzimidazole, 5-carboxybenzimidazole, 5-phenylbenzimidazole-2-thiol, (2-benzimidazolylthio)acetic acid, 2-(4-aminophenyl)benzimidazole, 2-(2-hydroxyphenyl)benzimidazole, 2-aminobenzothiazole, 2-mercaptobenzothiazole, 2-hydroxybenzothiazole, 5-aminobenzothiazole, 5-carboxybenzothi ...aminobenzothiazole, 5-carboxybenzothiazole, 5-aminobenzothiazole, 5-carboxybenzothiazole, 5-aminobenzothiazole, 5-carboxybenzothiazole, 5-aminobenzothiazole, 5-carboxybenzothiazole, 5-aminobenzothiazole, 5-carboxybenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5-aminobenzothiazole, 5 Examples of such benzothiazole include dibenzothiazole, 5-phenylbenzothiazole-2-thiol, (2-benzothiazolylthio)acetic acid, 2-(4-aminophenyl)benzothiazole, 2-(2-hydroxyphenyl)benzothiazole, 2-aminobenzoxazole, 2-mercaptobenzoxazole, 2-hydroxybenzoxazole, 5-aminobenzoxazole, 5-carboxybenzoxazole, 5-phenylbenzoxazole-2-thiol, (2-benzoxazolylthio)acetic acid, 2-(4-aminophenyl)benzoxazole, and 2-(2-hydroxyphenyl)benzoxazole. The compound having a monofunctional azole ring may have a structure in which these compounds further have a substituent.

[0051] Specific examples of compounds that can react with a compound having a bifunctional azole ring structure are shown below. Examples of the tetracarboxylic dianhydride include aromatic tetracarboxylic dianhydrides, aliphatic tetracarboxylic dianhydrides, and alicyclic tetracarboxylic dianhydrides.

[0052] The aromatic tetracarboxylic dianhydride is not particularly limited, but examples thereof include 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-cyclohexene-1,2-dicarboxylic dianhydride, pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-Diphenylsulfonetetracarboxylic dianhydride, 2,2',3,3'-Biphenyltetracarboxylic dianhydride, Methylene-4,4'-diphthalic dianhydride, 1,1'-Ethylidene-4,4'-diphthalic dianhydride, 2,2'-Propylidene-4,4'-diphthalic dianhydride, 1,2-Ethylene-4,4'-diphthalic dianhydride, 1,3-Trimethylene-4,4'-diphthalic dianhydride, 1,4-Tetramethylene-4,4'-diphthalic dianhydride, 1,5-Pentamethylene-4,4'-diphthalic dianhydride, 4,4'-Oxydi Phthalic dianhydride, thio-4,4'-diphthalic dianhydride, sulfonyl-4,4'-diphthalic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)benzene dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,3-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, 1,4-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, bis[3-(3,4-dicarboxypheno 2,2'-bis[3-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2'-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bis(3,4-dicarboxyphenoxy)dimethylsilane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1',3,3'-tetramethyldisiloxane dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,4,5,Examples of the dianhydride include 8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, and 1,2,7,8-phenanthrenetetracarboxylic dianhydride.

[0053] The aliphatic tetracarboxylic dianhydride is not particularly limited, but examples thereof include ethylene tetracarboxylic dianhydride, 1,2,3,4-butane tetracarboxylic dianhydride, and the like.

[0054] The alicyclic tetracarboxylic dianhydride is not particularly limited, and examples thereof include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, cyclohexane-1,2,3,4-tetracarboxylic dianhydride, cyclohexane-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-bicyclohexyl tetracarboxylic dianhydride, carbonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, methylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,2-ethylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,1'-ethylidene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, and 2,2'-propylidene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride. , oxy-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, thio-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, sulfonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, rel-[1S,5R,6R]-3-oxabicyclo[3,2,1]oct Examples of the dianhydride include tan-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, ethylene glycol-bis-(3,4-dicarboxylic dianhydride phenyl) ether, and 4,4'-biphenyl bis(trimellitic acid monoester dianhydride). Among aromatic tetracarboxylic dianhydrides, aliphatic tetracarboxylic dianhydrides, and alicyclic tetracarboxylic dianhydrides, it is preferable to use aromatic tetracarboxylic dianhydrides from the viewpoint of heat resistance.

[0055] As for the structure of the (B) basic polymer, from the viewpoint of suppressing the interaction between the ion-exchange group portion and the azole ring when forming a composition with the (A) perfluorocarbon polymer having an ion-exchange group, it is preferable to copolymerize a unit containing an azole ring with a unit not containing an azole ring. It is also preferable to copolymerize a base having an azole ring structure with an acid anhydride to form an oligomer, and then add a base not having an azole ring structure to further polymerize, that is, to perform two-stage polymerization, i.e., block copolymerization.

[0056] In the (B) basic polymer contained in the composition of the present embodiment, the content of the unit containing an azole ring relative to the total of the unit containing an azole ring and the unit not containing an azole ring is preferably 70 mol% or less, more preferably 55 mol% or less, and even more preferably 50 mol% or less, from the viewpoint of dispersibility. Also, from the viewpoint of chemical durability, the content is preferably 10 mol% or more, more preferably 15 mol% or more, even more preferably 18 mol% or more, and even more preferably 20 mol% or more.

[0057] The structure of the basic polymer (B) preferably contains a unit represented by formula (II).

[0058] [ka]

[0059] In formula (II), X 6 represents a tetravalent organic group, R 5 represents a divalent organic group, R 6 represents a divalent organic group or a single bond, and k is an integer of 1 to 1,000. In formula (II), X 6 is preferably a tetravalent aliphatic organic group or a tetravalent aromatic organic group having 6 to 50 carbon atoms. The number of carbon atoms in the organic group is preferably 6 to 36, more preferably 6 to 20. In addition, from the viewpoint of heat resistance, X 6 Preferably, contains an aromatic ring. In formula (II), R5 is preferably a divalent aliphatic organic group or a divalent aromatic organic group having 6 to 20 carbon atoms. The number of carbon atoms in the organic group is preferably 6 to 12, more preferably 6 to 10. In addition, from the viewpoint of heat resistance, R 5 Preferably, contains an aromatic ring. In formula (II), R 6 is preferably a single bond, or a divalent aliphatic organic group or aromatic organic group having 6 to 20 carbon atoms.

[0060] The structure of the basic polymer (B) more preferably contains a unit represented by formula (1).

[0061] [ka]

[0062] In formula (1), Y represents a tetravalent organic group.

[0063] The tetravalent organic group corresponding to Y in formula (1) is not particularly limited, but is preferably a tetravalent organic group represented by formula (D1).

[0064] [ka]

[0065] In formula (D1), X1 is selected from the following group.

[0066] [ka]

[0067] The molecular weight of the (B) basic polymer is, in terms of weight average molecular weight Mw, preferably 300 or more, more preferably 1000 or more, and even more preferably 5000 or more, from the viewpoint of heat resistance. The weight average molecular weight Mw is preferably 500000 or less, more preferably 300000 or less, and even more preferably 100000 or less, from the viewpoint of production stability. Here, the weight average molecular weight refers to a molecular weight measured by gel permeation chromatography using polystyrene of known number average molecular weight Mn as a standard. The molecular weight distribution Mw / Mn of the basic polymer (B) in this embodiment is preferably 2.60 or less, more preferably 2.50 or less, and even more preferably 2.40 or less. The lower limit of the molecular weight distribution is not particularly limited, and is usually 1.20 or more.

[0068] The terminal structure of the basic polymer is not particularly limited, and the raw materials used in the polymerization, such as carboxylic acids and amines, may be left as they are or may be further modified before use.

[0069] A solvent may be used in the synthesis of the basic polymer. The solvent is not particularly limited, but from the viewpoint of carrying out the reaction uniformly, aprotic solvents are preferable, such as N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, γ-butyrolactone, and N,N-dimethylsulfoxide.

[0070] The shape of the basic polymer (B) in this embodiment is not particularly limited, but is preferably particulate. The particulate basic polymer has good filterability, and when it is used as a composition containing the basic polymer together with the component (A), a high-viscosity composition in which the particles are unlikely to settle can be formed. The basic polymer (B) is more preferably particulate.

[0071] The method for microparticulating the (B) basic polymer is described below, but is not limited to the methods exemplified below, and any known pulverizing method can be used. Moreover, microparticulation can be performed by combining one or more methods. Examples of the pulverization method include freeze pulverization, dry jet mill, wet jet mill, hammer mill, vibration mill, roller mill, tumbling mill, pin disk mill, dry bead mill, wet bead mill, impact shear mill, high pressure fluid impingement mill, dry ball mill, wet ball mill, etc. Methods for obtaining fine particles of a basic polymer include a method of atomizing a basic polymer reaction solution by spray drying, a method of contacting the reaction solution with a poor solvent and precipitating in the form of fine particles, etc. The finely divided basic polymer can be used as it is, or can be used after being classified and the particle size distribution adjusted. Examples of the classification method include a method of passing through a mesh, a method of classifying particles according to the air resistance of the particles using an air flow, a method using centrifugal separation, and a method of classifying particles according to the moving speed of charged particles using an electric field, but the method is not limited to the above examples, and any known classification method can be used. When the grinding is carried out in a wet manner, any solvent can be used as long as it does not denature the basic polymer. A dispersant may be added within a range that does not affect the effects of this embodiment.

[0072] The particle size of the basic polymer (B) in this embodiment is preferably measured on a volume basis and evaluated as a primary particle size. Therefore, it is preferable to use an appropriate dispersion medium to disperse secondary aggregated particles, and evaluate the particle size of the particles dispersed using ultrasonic waves or the like. When the (B) basic polymer is in the form of fine particles, the proportion of the fine particles having a particle size exceeding 5.0 μm is, in terms of the proportion measured on a volume basis, preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less, from the viewpoint of the uniformity of the film when formed. When the basic polymer (B) is in the form of fine particles, the proportion of the fine particles having a particle size exceeding 3.0 μm is, in terms of the proportion measured on a volume basis, preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less, from the viewpoint of facilitating filtration of the composition.

[0073] When the (B) basic polymer is in the form of fine particles, the distribution of the fine particles is, from the viewpoint of improving chemical durability, such that the proportion of particles having a particle size in the range of 0.05 μm or more and 1.00 μm or less, measured on a volume basis, is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more.

[0074] When the (B) basic polymer is in the form of fine particles, the average diameter of the fine particles measured on a volume basis is preferably 5.00 μm or less, more preferably 3.00 μm or less, and even more preferably 2.00 μm or less, from the viewpoint of uniformity of the film when formed. From the viewpoint of smoothly pulverizing the fine particle slurry, the average value is preferably 0.10 μm or more, more preferably 0.12 μm or more, and further preferably 0.15 μm or more. In this specification, the term "fine particles" refers to particles having an average diameter of less than 7.5 μm, and particles having an average diameter of 7.5 μm or more are regarded as normal particles. The above-mentioned average diameter and particle size distribution can be measured by the method described in the Examples below. The average diameter and particle size distribution can be adjusted to the above-mentioned preferred range by the above-mentioned various known methods.

[0075] The composition of the present embodiment can be formed into an electrolyte membrane. That is, one of the present embodiments is an electrolyte membrane containing the composition of the present embodiment. The average diameter of the (B) basic polymer particles in the electrolyte membrane of the present embodiment can be measured by imaging the cross section of the electrolyte membrane in the thickness direction with a 2000x SEM (scanning electron microscope) and analyzing an area of ​​62.8 μm×26.0 μm. FIG. 11 is a 2000x SEM image of an area of ​​62.8 μm×26.0 μm. The analysis was performed using the image processing software ImageJ 1.50i, with a median filter of 2pix to remove noise, background processing by specifying Subtract background at 50pix, binarization by the Triangle method, and then analysis of all particles detected within the analysis field of view with Analyze Particles and output of the area of ​​each particle. Figure 12 shows the image after binarization, and Figure 13 shows the image after the particle parts were analyzed and extracted with Analyze Particles. Next, the particle diameter d was calculated from the area of ​​each output particle, assuming that each particle was a circle. That is, the value of d was calculated for each particle so that S=d / 2×d / 2×π, where S is the area of ​​the particle and d is the particle diameter when the particle is assumed to be circular. Furthermore, the range of particle diameter d was divided into 100 equal parts from 0 nm to 10,000 nm, and the number of particles in each 100 nm interval was counted. The average particle diameter d was calculated from the counted results, and the average size of the basic polymer particles was obtained. The average particle size of the (B) basic polymer in the film obtained by the above analysis is preferably 5.00 μm or less, more preferably 3.00 μm or less, and even more preferably 2.00 μm or less, from the viewpoint of improving the chemical durability of the film when formed. Also, the average particle size is preferably 0.10 μm or more, more preferably 0.12 μm or more, and even more preferably 0.15 μm or more, from the viewpoint of smoothly pulverizing the fine particle slurry.

[0076] Regarding the particle size of the basic polymer in the film, the ratio of particles obtained by the above analysis that have a particle diameter d exceeding 5.0 μm is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less, from the viewpoint of the uniformity of the film when formed. Also, regarding the particle size of the basic polymer, the ratio of particles that have a particle diameter d exceeding 3.0 μm is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less, from the viewpoint of the uniformity of the film. Regarding the distribution of the basic polymer in the film, from the viewpoint of improving chemical durability, of the particles obtained by the above-mentioned analysis, the particles having a particle diameter d in the range of 0.05 μm or more and 1.00 μm or less are preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more.

[0077] The coefficient of variation for the electrolyte membrane of this embodiment can be calculated from the standard deviation and average value of the particle diameter obtained by the above-mentioned analysis. That is, the coefficient of variation can be obtained from the following formula: coefficient of variation = standard deviation / average value. From the viewpoint of membrane formability, the coefficient of variation of the particle diameter of the basic polymer in the membrane is preferably 0.10 or more, more preferably 0.20 or more, and even more preferably 0.30 or more. Moreover, from the viewpoint of improving the strength of the membrane, the coefficient of variation is preferably 2.00 or less, more preferably 1.80 or less, even more preferably 1.50 or less, and even more preferably 1.40 or less.

[0078] The basic polymer contained in the composition of the present embodiment may be a mixture of two or more basic polymers. The method for preparing the composition of the present embodiment is not particularly limited as long as it is a method that can uniformly mix (A) the perfluorocarbon polymer having an ion exchange group and (B) the basic polymer, and can be mixed by a known method. The method for preparing the composition is not limited to the following, but examples thereof include a method of stirring with a magnetic stirrer, a method of stirring with a stirring blade, a method of mixing with a static mixer, and a method of mixing with centrifugal force.

[0079] The composition of the present embodiment may contain a solvent capable of suspending the perfluorocarbon polymer having an ion exchange group (A) as necessary. Examples of the solvent include water; protic organic solvents such as ethanol, methanol, n-propanol, isopropyl alcohol, butanol, and glycerin; and aprotic organic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. These may be used alone or in combination of two or more.

[0080] The composition can be concentrated to adjust the viscosity depending on the forming method and / or application of the electrolyte membrane. The concentration method is not particularly limited, but examples include a method of heating the composition to evaporate the solvent and a method of concentrating under reduced pressure. The viscosity measured at 25°C is preferably 100 cP or more, more preferably 300 cP or more, and even more preferably 500 cP or more, from the viewpoint of facilitating the membrane formation process. The viscosity is preferably 5000 cP or less, more preferably 4000 cP or less, and even more preferably 3500 cP or less, from the viewpoint of facilitating the adjustment of the membrane thickness.

[0081] If necessary, a third component may be added to the composition of the present embodiment. The third component is not particularly limited, but examples thereof include a hydrocarbon polymer electrolyte, a thioether compound, a metal ion, a porous body, etc. Each example will be described below.

[0082] (Hydrocarbon-based polymer electrolyte) From the viewpoint of chemical durability, the content of component A in the composition of the present embodiment is preferably 100 mass % based on the total polymer used as the polymer electrolyte. The composition of the present embodiment may contain, in addition to the component A, for example, a hydrocarbon-based polymer electrolyte or the like in any ratio. The hydrocarbon-based polymer electrolyte is not particularly limited as long as it is a hydrocarbon-based polymer having an ion exchange group, and examples thereof include polyphenylene sulfide, polyphenylene ether, polysulfone, polyether sulfone, polyether ether sulfone, polyether ketone, polyether ether ketone, polythioether ether sulfone, polythioether ketone, polythioether ether ketone, polybenzimidazole, polybenzoxazole, polyoxadiazole, polybenzoxazinone, polyxylylene, polyphenylene, polythiophene, polypyrrole, polyaniline, polyacene, polycyanogen, polynaphthyridine, polyphenylene sulfide sulfone, polyphenylene sulfone, polyimide, polyetherimide, polyesterimide, polyamideimide, polyarylate, aromatic polyamide, polystyrene, polyester, polycarbonate, etc. The content of the hydrocarbon-based polymer electrolyte is preferably 50% by mass or less, and more preferably 20% by mass or less, based on the total amount of polymers used as the polymer electrolyte.

[0083] (Thioether compounds) The composition of the present embodiment may contain a thioether compound. The thioether compound in the present embodiment is a compound having a chemical structure of -(RS)r- (S is a sulfur atom, R is a hydrocarbon group, and r is an integer of 1 or more). Specific examples of the thioether compound include, but are not limited to, dialkyl thioethers such as dimethyl thioether, diethyl thioether, dipropyl thioether, methyl ethyl thioether, and methyl butyl thioether; cyclic thioethers such as tetrahydrothiophene and tetrahydroapyran; aromatic thioethers such as methyl phenyl sulfide, ethyl phenyl sulfide, diphenyl sulfide, and dibenzyl sulfide; etc. The thioether compounds exemplified here may be used as they are, or a polymer obtained by using the exemplified compounds as a monomer, such as polyphenylene sulfide (PPS), may be used as the thioether compound.

[0084] From the viewpoint of durability, the thioether compound is preferably a polymer (oligomer, polymer) having r of 10 or more, more preferably a polymer having r of 1,000 or more. A particularly preferred thioether compound is polyphenylene sulfide (PPS). As the polyphenylene sulfide that can be preferably used in the present embodiment, there is mentioned polyphenylene sulfide having preferably 70 mol % or more, more preferably 90 mol % or more of a paraphenylene sulfide skeleton.

[0085] The method for producing the polyphenylene sulfide is not particularly limited, and examples thereof include a method of polymerizing a halogen-substituted aromatic compound (such as p-dichlorobenzene) in the presence of sulfur and sodium carbonate, a method of polymerizing a halogen-substituted aromatic compound in the presence of sodium sulfide or sodium hydrogen sulfide and sodium hydroxide in a polar solvent, a method of polymerizing a halogen-substituted aromatic compound in the presence of hydrogen sulfide and sodium hydroxide or sodium aminoalkanoate in a polar solvent, or a method of self-condensation of p-chlorothiophenol. Among these, a method of reacting sodium sulfide with p-dichlorobenzene in an amide solvent such as N-methylpyrrolidone or dimethylacetamide or a sulfone solvent such as sulfolane is preferably used.

[0086] The polyphenylene sulfide preferably contains an -SX group, in which S represents a sulfur atom and X represents an alkali metal atom or a hydrogen atom. The content of -SX groups in polyphenylene sulfide is usually 10 μmol / g to 10,000 μmol / g, preferably 15 μmol / g to 10,000 μmol / g, and more preferably 20 μmol / g to 10,000 μmol / g. The content of -SX group in the above range means that there are many reactive active sites. By using polyphenylene sulfide whose content concentration of -SX group satisfies the above range, miscibility with the component A contained in the composition of the present embodiment is improved. Therefore, it is considered that the dispersibility of polyphenylene sulfide in the composition is improved, and the electrolyte membrane obtained from the composition has higher durability under high temperature and low humidity conditions.

[0087] In addition, as the thioether compound, one having an acidic functional group introduced at the end can also be suitably used. The acidic functional group to be introduced is preferably selected from the group consisting of a sulfonic acid group, a phosphoric acid group, a carboxylic acid group, a maleic acid group, a maleic anhydride group, a fumaric acid group, an itaconic acid group, an acrylic acid group, and a methacrylic acid group, and more preferably a sulfonic acid group. The method of introducing an acidic functional group is not particularly limited, and a general method is used. For example, when introducing a sulfonic acid group into a thioether compound, it can be introduced under known conditions using a sulfonating agent such as sulfuric anhydride or fuming sulfuric acid. More specifically, it can be introduced under the conditions described in K. Hu, T. Xu, W. Yang, Y. Fu, Journal of Applied Polymer Science, Vol. 91, or E. Montoneri, Journal of Polymer Science: Part A: Polymer Chemistry, Vol. 27, 3043-3051 (1989). In addition, compounds in which the introduced acidic functional group is further substituted with a metal salt or an amine salt can also be suitably used as the thioether compound. As the metal salt, alkali metal salts such as sodium salt and potassium salt, and alkaline earth metal salts such as calcium salt are preferred.

[0088] Furthermore, when the thioether compound is used in a powder form, the average particle size of the thioether compound is preferably 0.01 μm to 10.0 μm, more preferably 0.01 μm to 5.0 μm, even more preferably 0.01 μm to 3.0 μm, and even more preferably 0.01 μm to 2.0 μm, in order to improve the dispersibility in the composition and thereby realize the effect of extending the life, etc. The average particle size of the thiol compound is a value measured by a laser diffraction / scattering type particle size distribution measuring device (for example, model number LA-950 manufactured by Horiba, Ltd.).

[0089] Examples of methods for finely dispersing a thioether compound in a composition include a method of applying high shear during melt-kneading of a thioether compound with component A and component B, pulverizing and finely dispersing the compound, and a method of obtaining a mixed solution of a thioether compound with component A and component B, filtering the solution to remove coarse thioether compound particles, and using the filtered solution. The melt viscosity of polyphenylene sulfide preferably used when melt-kneading is preferably 1 to 10,000 poise, more preferably 100 to 10,000 poise, from the viewpoint of moldability. The melt viscosity is a value obtained by using a flow tester at 300°C, a load of 196N, and L / D (L: orifice length, D: orifice inner diameter) = 10 / 1 for 6 minutes.

[0090] The ratio (Wa / Wd) of the mass (Wa) of the A component (total amount of the A component contained in the composition) to the mass (Wd) of the thioether compound is preferably 60 / 40 to 99.99 / 0.01, more preferably 70 / 30 to 99.95 / 0.05, even more preferably 80 / 20 to 99.9 / 0.1, and even more preferably 90 / 10 to 99.5 / 0.5. By making the mass ratio 60 or more, better ion conductivity can be realized, and better battery characteristics can be realized. On the other hand, by making the mass ratio of the thioether compound 40 or less, durability in battery operation under high temperature and low humidity conditions can be improved.

[0091] (Metal ions) In order to further improve chemical durability, the composition of the present embodiment may contain metal ions, preferably transition metal ions. The transition metal ion is not particularly limited, but examples thereof include scandium ion, titanium ion, vanadium ion, chromium ion, manganese ion, iron ion, cobalt ion, nickel ion, copper ion, zinc ion, yttrium ion, zirconium ion, niobium ion, molybdenum ion, technetium ion, ruthenium ion, rhodium ion, palladium ion, silver ion, cadmium ion, lanthanum ion, cerium ion, praseodymium ion, neodymium ion, promethium, samarium ion, europium ion, gadolinium ion, terbium ion, dysprosium ion, holmium ion, erbium ion, thulium ion, ytterbium ion, lutetium ion, hafnium ion, tantalum ion, tungsten ion, rhenium ion, osmium ion, iridium ion, platinum ion, and gold ion. From the viewpoint of effectively improving the decomposition function of hydrogen peroxide, cerium ion is preferable. The cerium ion may be in a +3 or +4 valence state, but is not particularly limited in this embodiment.

[0092] (Porous body) The composition or electrolyte membrane of the present embodiment may be reinforced by incorporating a porous body into the composition or electrolyte membrane by a known method. Examples of known reinforcement methods include, but are not limited to, reinforcement by adding fibril-like PTFE (JP Patent Publication No. 53-149881 and JP Patent Publication No. 63-61337), reinforcement by a stretched PTFE porous membrane (see JP Patent Publication No. 5-75835 and JP Patent Publication No. 11-501964), reinforcement by an electrolytic spun membrane (JP Patent Publication No. 2008-243420), and reinforcement by a wet phase separation membrane (JP Patent Publication No. 2003-297393).

[0093] The composition of the present embodiment can be used after filtering the composition for the purpose of removing foreign matter in component A, foreign matter in component B, and foreign matter in other components, etc. The filtering method is not particularly limited, but may be, for example, pressure filtration.

[0094] The solid content concentration in the composition of the present embodiment is not particularly limited, but from the viewpoint of facilitating the formation of an electrolyte membrane, it is preferably 5% or more, more preferably 8% or more, and even more preferably 10% or more. Also, from the viewpoint of facilitating filtration, the solid content concentration is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less. The solids concentration can be measured as follows. First, the mass W0 of the weighing bottle is precisely weighed. Approximately 10 g of the object to be measured is placed in the weighing bottle, precisely weighed, and designated as W1. The object to be measured is dried at 110°C and 0.10 MPa or less for 3 hours or more, cooled in a desiccator containing silica gel, and after it has reached room temperature, precisely weighed without allowing it to absorb water, and designated as W2. (W2-W0) / (W1-W0) is expressed as a percentage, and the above is measured a total of 5 times, and the average is designated as the solids concentration.

[0095] <Electrolyte membrane> The electrolyte membrane of the present embodiment includes the composition of the present embodiment. The electrolyte membrane of the present embodiment is formed by forming the composition of the present embodiment. The electrolyte membrane of the present embodiment exhibits excellent chemical durability.

[0096] The thickness of the electrolyte membrane of the present embodiment is not particularly limited, but from the viewpoint of gas permeability, it is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 5 μm or more. From the viewpoint of improving electrical conductivity, the thickness is preferably 500 μm or less, more preferably 100 μm or less, and further preferably 50 μm or less.

[0097] From the viewpoint of heat resistance during fuel cell operation, the electrolyte membrane of this embodiment preferably has a glass transition temperature of 80° C. or higher, more preferably 100° C. or higher, even more preferably 120° C. or higher, and even more preferably 130° C. or higher. The glass transition temperature of the electrolyte membrane is measured in accordance with JIS-C-6481. Specifically, the electrolyte formed into a membrane is cut into a width of 5 mm, and the test piece is heated from room temperature at a rate of 2°C / min using a dynamic viscoelasticity measuring device, and the dynamic viscoelasticity and loss tangent of the test piece are measured using the viscoelasticity measuring device. The peak temperature of the measured loss tangent is taken as the glass transition temperature. This glass transition temperature can be adjusted by controlling the structure, molecular weight, ion exchange capacity, etc. of the perfluorocarbon polymer (A) having an ion exchange group contained in the composition.

[0098] The electrolyte membrane of the present embodiment may be reinforced using a porous membrane made by a known technique, such as fibril PTFE, a stretched PTFE porous membrane, a nanofiber sheet obtained by electrospinning an organic resin, a membrane obtained by melt-spinning an organic resin, or a woven fabric with fibers woven therein.

[0099] (Method of manufacturing electrolyte membrane) The electrolyte membrane of the present embodiment can be obtained by forming the composition of the present embodiment into a membrane by a known membrane forming method, which is not particularly limited, and may be, for example, a method using a knife coater, a blade coater, a dip coater, a gravure roll coater, a chamber doctor coater, a natural roll coater, a reverse roll coater, or the like. After the electrolyte membrane of the present embodiment is formed as described above, it is preferable to further perform a heat treatment from the viewpoint of mechanical strength. The heat treatment temperature is preferably 100° C. to 230° C., more preferably 110° C. to 230° C., and further preferably 120° C. to 200° C. The heat treatment time varies depending on the heat treatment temperature, but from the viewpoint of obtaining a polymer electrolyte membrane having high durability, it is preferably 5 minutes to 3 hours, and more preferably 10 minutes to 2 hours.

[0100] <Membrane electrode assembly> The membrane electrode assembly of the present embodiment includes the electrolyte membrane of the present embodiment, and therefore the membrane electrode assembly of the present embodiment can exhibit excellent chemical durability. As described above, when the electrolyte membrane of the present embodiment is used in a polymer electrolyte fuel cell, it can be used as a membrane electrode assembly (hereinafter referred to as "MEA") in which two types of electrode catalyst layers, an anode and a cathode, are joined together. An MEA is also defined as an assembly in which a pair of gas diffusion layers are joined to the outer sides of the electrode catalyst layers so as to face each other.

[0101] The dispersion of particles in the MEA or electrolyte membrane of this embodiment can be confirmed by observing the cross section with an SEM, etc. A known method can be used for cutting the cross section, and for example, by using a freeze cutting method (cryomicrotome method), the cross section of the electrolyte can be observed with minimal deformation of the internal structure. In addition, the particles were analyzed by using an X-ray microanalyzer to analyze the elements of the particle part observed on the cross section of the electrolyte, or by sampling the particles by microsampling and analyzing them with IR to determine the constituent elements of the particles and the 1780 cm -1 The peak near 1720 cm -1 You can see the nearby peaks. As described above, it can be confirmed that the electrolyte membrane or MEA of this embodiment contains the composition of this embodiment.

[0102] <Composite membrane> The electrolyte membrane of the present embodiment can be combined with other membranes to form a composite membrane. Examples of the other membranes include membranes containing polyimide. That is, the composite membrane of the present embodiment is a composite membrane including the electrolyte membrane of the present embodiment and a membrane containing polyimide. In addition, the polyimide is preferably a polyimide represented by formula (1). The polyimide-containing film is preferably in the form of a fiber sheet.

[0103] <<Second embodiment>> [Composition] The composition of the present embodiment is a composition containing a polyimide having a structure represented by formula (1) (hereinafter, also referred to as "polyimide in the present embodiment"). The polyimide in the present embodiment may contain a structural unit other than the structure represented by formula (1).

[0104] [ka] (In formula (1), Y represents a tetravalent organic group.)

[0105] The composition of the present embodiment may be in the form of a varnish containing the polyimide of the present embodiment and a solvent, or may be in the form of a solid containing the polyimide of the present embodiment and other polymers or fillers. The composition of the present embodiment may be in the form of a varnish to be made into a solid by various known methods. The composition of the present embodiment exhibits excellent durability even under high temperature and low humidity conditions. In addition, the composition of the present embodiment has high affinity with perfluoro-based proton exchange membranes having acidic groups such as sulfonic acid groups and carboxylic acid groups. In particular, a composite membrane formed by using the composition of the present embodiment as a core material of an electrolyte membrane exhibits excellent durability and ion conductivity even under high temperature and low humidity conditions. Therefore, the composition of the present embodiment can be suitably used as a core material of an electrolyte membrane.

[0106] The polyimide in this embodiment is preferably a polyimide having a structure represented by formula (7) or (8).

[0107] [ka] (In formula (7), A represents a divalent organic group, Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:30.)

[0108] [ka] (In formula (8), Y and D represent tetravalent organic groups, and the ratio of k:l is 20:80 to 70:30.)

[0109] The polyimide of formula (7) in this embodiment includes repeating units 1 present in the number m and repeating units 2 present in the number n, and it is considered that repeating units 1 contribute to the strength and solubility of the core material, and repeating units 2 contribute to the strength and compatibility with the electrolyte membrane of the core material. In particular, it is considered that the imidazole group in repeating unit 2 contributes to the compatibility with the polytetrafluoroethylene (PTFE)-based electrolyte membrane. Thus, from the viewpoint of ensuring the solubility in the solvent and the compatibility with the electrolyte membrane, the ratio of m:n in formula (7) is preferably 20:80 to 70:30, more preferably 25:75 to 65:35, and even more preferably 30:70 to 60:40. The polyimide of formula (8) in this embodiment includes repeating units 3 present in the number k and repeating units 4 present in the number l, and it is considered that repeating units 3 contribute to the strength when used as a core material, and repeating units 4 contribute to solubility. In addition, the imidazole groups present in both repeating units 3 and 4 are considered to contribute to compatibility, similar to the polyimide of formula (7). Thus, from the viewpoint of ensuring solubility in a solvent, compatibility with an electrolyte, and strength, the ratio of k:l in formula (8) is preferably 20:80 to 70:30, more preferably 25:75 to 65:35, and even more preferably 30:70 to 60:40. The more the amount of imidazole groups in the polyimide, the more the flatness of the molecular structure improves and the lower the solubility tends to be. Therefore, from the viewpoint of storage stability of the solution, the proportion of imidazole groups in the polyimide is preferably 50 mol % or less.

[0110] The divalent organic group represented by A in formula (7) is not particularly limited, but from the viewpoint of solubility in a solvent, it is preferably a divalent organic group represented by formula (A-1), (A-2), (A-3) or (A-4).

[0111] [ka] (In formulae (A-1), (A-3), and (A-4), X1 represents a divalent organic group selected from the group represented by the following formulae (X1-1) to (X1-10), and X2 in formula (X1-10) represents a divalent organic group selected from the group represented by formulae (X2-1) to (X2-7). In formulae (A-2) and (A-3), L represents a methyl group or a trifluoromethyl group, and in formula (A-4), R represents a hydroxyl group.)

[0112] [ka] (In formulas (X1-2) and (X2-2), a represents the number of repeating units and is an integer of 1 to 5.)

[0113] Each benzene ring in the above formulae (X1-8) to (X1-10) may have a substituent such as a methyl group, an ethyl group, a methoxy group, a trifluoromethyl group, or a halogen atom. Although polyimides are generally poorly soluble in solvents, polyimides having structures represented by the above formulas (7) and (8) have excellent solubility, and therefore the composition of the present embodiment can be easily made into a polyimide solution containing a solvent. The polyimide solution can be easily processed into a polyimide porous membrane, nanofiber, film, etc., by simply removing the solvent, and therefore has excellent processability compared to polyimides that are poorly soluble in solvents and solutions of polyimide precursors that require an imidization process. In particular, the porous membrane and nanofiber can be suitably used as the core material of an electrolyte membrane.

[0114] In addition, in this embodiment, from the viewpoint of solubility, it is particularly preferable that A is represented by the following formula (A1).

[0115] [ka]

[0116] That is, the polyimide in this embodiment is preferably a polyimide having a structure represented by formula (5).

[0117] [ka] (In formula (5), Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:30.)

[0118] In the above formulas (1), (7), and (8), the tetravalent organic group corresponding to Y and D is not particularly limited, but is preferably a tetravalent organic group represented by formula (D1) from the viewpoints of the solubility in a solvent of the polyimide having the structure represented by formulas (1), (7), and (8) and the strength when used as a core material.

[0119] [ka] (In formula (D1), X1 has the same meaning as X1 in formula (A-1) above.)

[0120] X1 in D1 is preferably a divalent organic group represented by the formula (X1-1) or (X1-2); [ka] It is preferable that:

[0121] Generally, polyimides can be synthesized by a condensation reaction between a diamine and an acid dianhydride. The imidazole structure of the polyimide in this embodiment can be typically introduced into the polyimide by reacting 5-amino-2-(4-aminophenyl)benzimidazole with an acid dianhydride, but is not limited thereto, and can be synthesized as described below.

[0122] A in the polyimide in this embodiment can be, for example, a structure obtained from a diamine, and is not limited to the following, but may be derived from 4,4'-oxydianiline (hereinafter, also referred to as 4,4'-ODA), 3,4'-oxydianiline (hereinafter, also referred to as 3,4'-ODA), 4,4'-methylenebisaniline (hereinafter, also referred to as 4,4'-DDM), 3,3' -methylenebisaniline (3,3'-DDM), 4,4'-diaminobenzophenone (4,4'-DADPM), 3,3'-diaminobenzophenone (3,3'-DADPM), 4,4'-diaminodiphenyl sulfide (4,4'-ASD), 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 4,4'-diaminodiphenyl sulfone (4,4'-DiaminoDiphenyl Sulfone (hereinafter also referred to as 4,4'-DDS), 4,4'-(Hexafluoroisopropylidene)dianiline (hereinafter also referred to as 6FAP), 4,4'-isopropylidenedianiline, 1,4-bis(4-aminophenoxy)benzene (hereinafter also referred to as TFE-Q), 1,3-bis(4-aminophenoxy)benzene (hereinafter also referred to as TFE-R), 4,4'-bis(4-aminophenoxy)biphenyl (hereinafter also referred to as BAPB), 2,2-bis{4-(4-aminophenoxy)phenyl}propane (2,2-Bis{4-(4-aminophenoxy)phenyl}propane (hereinafter referred to as BAPP), 2,2-Bis{4-(4-aminophenoxy)phenyl}hexafluoropropane (hereinafter referred to as HFBAPP), bis{4-(4-aminophenoxy)phenyl}sulfone (hereinafter referred to as BAPS), bis{4-(3-aminophenoxy)phenyl}sulfone (hereinafter referred to as BAPS-M), 4,4'-diaminophenoxyphenyl}sulfone (hereinafter referred to as BAPS-M), bis{4-(4-aminophenoxy) ... The following compounds are derived from 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (hereinafter referred to as TFMB), 4,4'-diamino-2,2'-dimethylbiphenyl (hereinafter referred to as m-TB), 4,4'-diamino-2,2'-dimethoxybiphenyl (hereinafter referred to as m-DS), and 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether (hereinafter referred to as m-DS): ether (hereinafter referred to as BTFDPE), 1,4-Bis{4-amino-2-(trifluoromethyl)phenoxy}benzene (hereinafter referred to as FAPQ), 2,2-bis(3-amino-4-hydroxyphenyl)propane (hereinafter referred to as BPA-DA), 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (hereinafter referred to as 6FHA), 2,Examples of such divalent organic groups include those derived from 2,2-bis(3-amino-4-methylphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone (hereinafter also referred to as BPS-DA), and 4,4'-diamino-3,3'-dimethyldiphenylmethane. By using these when polyimidizing, a structure corresponding to the above A can be obtained. The above-mentioned structures may contain one type alone, or may contain two or more types in any order.

[0123] In the present embodiment, B and D in the polyimide can be each independently a structure obtained from, for example, an acid dianhydride, and are not limited to the following, but include structures derived from 4,4'-oxydiphthalic anhydride (hereinafter also referred to as ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (hereinafter also referred to as BTDA), 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride (hereinafter also referred to as DSDA), 4,4'-(hexafluoroisopropylidene)diphthalic ... Anhydride (hereinafter, also referred to as 6FDA)-derived tetravalent organic groups can be used, and by using these in polyimidization, a structure corresponding to the above B can be obtained. The above-mentioned structures may contain one type alone, or may contain two or more types in any order.

[0124] D in the present embodiment can be, for example, a structure obtained from an acid dianhydride, and examples thereof include the structures exemplified above for B. Particularly preferred is 6FDA from the viewpoint of solubility.

[0125] In the present embodiment, from the viewpoint of solubility, it is preferable that B or D is each independently represented by formula (B1), and it is more preferable that B or D is represented by formula (Y1).

[0126] [ka]

[0127] The polyimide in this embodiment is preferably a polyimide having a structure represented by formula (6).

[0128] [ka] (In formula (6), Y represents a tetravalent organic group, k and l represent the numbers of repeating units, and the ratio of k:l is 20:80 to 70:30.)

[0129] In the present embodiment, the tetravalent organic group is also preferably an organic group having an alicyclic structure. Examples of the alicyclic structure include 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 4-(2,5-dioxotetrahydrofurane-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, etc. The above-mentioned acid dianhydrides may be used alone or in combination of two or more. When A contains groups derived from two or more dianhydrides, these groups may appear in any order.

[0130] The weight average molecular weight of the polyimide in this embodiment is not particularly limited, but from the viewpoint of heat resistance, it is preferably 300 or more, more preferably 1000 or more, and even more preferably 5000 or more. From the viewpoint of production stability, the weight average molecular weight is preferably 500000 or less, more preferably 300000 or less, and even more preferably 100000 or less. Here, the weight average molecular weight refers to a molecular weight measured by gel permeation chromatography using polystyrene of a known number average molecular weight as a standard. The molecular weight distribution Mw / Mn of the polyimide in this embodiment is preferably 2.60 or less, more preferably 2.50 or less, and further preferably 2.40 or less. The lower limit of the molecular weight distribution is not particularly limited, and is usually 1.50 or more.

[0131] Furthermore, when the composition of this embodiment is used to manufacture a processed body such as a porous body or a fiber sheet, the amount of residual volatile components in the processed body is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 3 mass % or less, from the viewpoint of the electrical properties when used as a composite membrane. The content of the residual volatile components is expressed as the weight loss rate at 30° C. to 350° C. in a nitrogen atmosphere, and specifically, can be measured by the method described in the examples. The residual volatile content of the fiber sheet can be adjusted to 10% by mass or less, for example, by providing a heat treatment step after producing a processed body such as a fiber sheet. The amount of the remaining volatile components can be specifically measured by the method described in the Examples below.

[0132] The polyimide in this embodiment is not particularly limited, but can be synthesized, for example, as follows. That is, the acid dianhydride component and the diamine component as exemplified above are dissolved in an organic solvent, an azeotropic solvent such as toluene is added, and water generated during imidization is removed from the system, so that the composition of this embodiment containing polyimide and solvent (also called polyimide varnish) can be produced. Here, the reaction conditions are not particularly limited, but for example, the reaction temperature is 0°C to 200°C, and the reaction time is 3 to 72 hours. In order to sufficiently proceed with the reaction with the sulfone group-containing diamines, it is preferable to heat the reaction at 180°C for about 12 hours. The reaction may be carried out in air, but is preferably in an inert atmosphere such as argon or nitrogen. An imidization catalyst such as pyridine, triethylamine, imidazole, or acetic anhydride may be used in the reaction.

[0133] In this embodiment, diamines and acid dianhydrides other than those described above can also be used. For example, diamines include, but are not limited to, those derived from p-phenylenediamine (hereinafter also referred to as p-PD), 4,4'-diaminobenzanilide (hereinafter also referred to as DABA), 1,4-cyclohexanediamine, and 1,2-cyclohexanediamine. Acid dianhydrides include, but are not limited to, those derived from pyromellitic anhydride (hereinafter also referred to as PMDA), diphenyltetracarboxylic dianhydride (4,4'-biphthalic anhydride), and diphenyltetracarboxylic dianhydride (4,4'-biphthalic anhydride). anhydride (hereinafter also referred to as BPDA), 9,9-diphenylfluorene dianhydride (hereinafter also referred to as DPFLDA), hydroxypyromellitic dianhydride (hereinafter also referred to as HPMDA), bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (hereinafter also referred to as BODA), and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione (hereinafter also referred to as TDA). In particular, from the viewpoint of improving the heat resistance and strength of the polyimide, it is preferable that the polyimide contains p-PD, DABA, PMDA, or BPDA, and from the viewpoint of ensuring the solubility of the polyimide in a solvent and the compatibility with an electrolyte, the content of the polyimide is preferably 20 mol % or less relative to the above formula (1). From the viewpoint of increasing the solubility of the polyimide in a solvent, it is preferable that the polyimide contains an aromatic acid dianhydride (DPFLDA), an alicyclic acid dianhydride (HPMDA, BODA, TDA), or an alicyclic diamine (cyclohexanediamine) having a bulky functional group, and from the viewpoint of not impairing the heat resistance and strength of the polyimide, the amount of the aromatic acid dianhydride is preferably 20 mol % or less relative to the above formula (1).

[0134] The polyimide in this embodiment may contain structural units other than the repeating unit 1 and repeating unit 2 described above, as long as the performance of the polyimide is not impaired.

[0135] The solvent is not particularly limited as long as it dissolves the polyimide in this embodiment. Known reaction solvents include, but are not limited to, at least one polar solvent selected from phenolic solvents such as m-cresol, amide solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and equamide, lactone solvents such as γ-butyrolactone (GBL), δ-valerolactone, ε-caprolactone, γ-crotonolactone, γ-hexanolactone, α-methyl-γ-butyrolactone, γ-valerolactone, α-acetyl-γ-butyrolactone, and δ-hexanolactone, sulfoxide solvents such as N,N-dimethylsulfoxide (DMSO), ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, and ester solvents such as methyl acetate, ethyl acetate, butyl acetate, and dimethyl carbonate. Among these, from the viewpoint of solubility, NMP, GBL, DMF and DMAc are preferred, and NMP, DMF and DMAc are more preferred.

[0136] A specific example of a method for preparing the composition of this embodiment containing a polyimide and a solvent is as follows. First, 5-amino-2-(4-aminophenyl)benzimidazole and 3,3'-diaminodiphenylsulfone are placed in a separable flask equipped with a reflux tube in a molar ratio of 50:50, and NMP is added as a solvent to dissolve. Then, 4,4'-oxydiphthalic dianhydride is added at 95-105 mol% relative to the diamine to obtain a solution with a solid content of 30 mass%. Then, the temperature inside the flask is heated to 180°C, toluene is added at 15 mass% relative to the solution, and after refluxing for 2 hours, the water accumulated in the reflux tube is distilled off. Then, the temperature inside the flask is heated to 180°C for 5 hours, and an NMP varnish (composition) of polyimide having a structure represented by formula (1) can be obtained. Even if GBL, DMF, or DMAc is used as the solvent, a varnish (composition) of polyimide having a structure represented by formula (1) can be obtained by the same method.

[0137] Additives may be added to the polyimide varnish in this embodiment as appropriate. Examples of additives include inorganic particles such as cerium oxide and strontium carbonate, and organic compounds such as polystyrene, polyvinylnaphthalene, polymethyl methacrylate, cellulose triacetate, and fluorene derivatives. Other examples include inorganic salts for improving processability, organic salts, leveling agents, dispersants, surfactants, adhesion aids, and flame retardants for imparting flame retardancy. Further examples include antioxidants, ultraviolet inhibitors, light stabilizers, plasticizers, waxes, fillers, pigments, dyes, foaming agents, defoamers, dehydrating agents, antistatic agents, antibacterial agents, and antifungal agents. The additives added to the polyimide varnish may be directly contained in the processed body such as the core material.

[0138] The polyimide varnish of this embodiment can be processed into various shapes such as, for example, a film, a porous body, and a nanofiber by various known methods, but is not limited to the following. That is, the processed body of this embodiment contains the composition of this embodiment, and such a processed body may have various shapes such as a film, a porous body, and a nanofiber, and in particular, the porous body and the nanofiber can be suitably used as a core material for reinforcing an electrolyte membrane for a fuel cell. In addition to the above, the processed body of this embodiment can be used for various applications such as a fiber sheet, a wet phase separation membrane, and an additive as particles.

[0139] The porous body and fiber sheet of this embodiment can be formed by, for example, various known methods, but are not limited to the following. That is, the porous body of this embodiment contains the polyimide of this embodiment, and such a porous body may have various shapes such as a porous membrane and a fiber sheet, and the fiber sheet can be suitably used as a core material that reinforces an electrolyte membrane for a fuel cell. In addition to the above, the porous body of this embodiment can be used for various applications such as a wet phase separation membrane and an additive as particles.

[0140] The method for producing a porous body is not particularly limited, and various known methods can be adopted. Examples of the method for producing a porous body include a thermally induced phase separation method and a non-solvent induced phase separation method for producing a porous body using phase separation. In addition, the method for producing a porous body as a fiber sheet is not particularly limited, and various known methods can be adopted. Examples of the method for producing a porous body as a fiber sheet include a method for producing a nonwoven fabric, such as an electrospinning deposition method (also called an electrospray deposition method), a melt blow method, a spunbond method, and a papermaking method. The mechanical strength of the fiber sheet, which is a nonwoven fabric, can be increased by subjecting it to heat treatment, press treatment, calendar treatment, plasma treatment, infrared irradiation, ultraviolet irradiation, electron beam irradiation, gamma ray irradiation, or the like.

[0141] When the porous body of this embodiment is produced as a fiber sheet, the average fiber diameter of the fiber sheet is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 700 nm or less, from the viewpoint of facilitating embedding in the proton conductive polymer. Also, the average fiber diameter of the fiber sheet is preferably 100 nm or more and 1000 nm or less, more preferably 100 nm or more and 500 nm or less, and even more preferably 200 nm or more and 350 nm or less, in order to accommodate dimensional changes when made into a composite membrane.

[0142] From the viewpoint of maintaining strength, the thickness of the fiber sheet of the present embodiment is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 8 μm or more. From the viewpoint of improving the proton conductivity of the composite membrane, the thickness of the fiber sheet is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less.

[0143] The fiber sheet of the present embodiment preferably has a basis weight of 1.5 g / m from the viewpoint of maintaining strength. 2 More preferably, 1.8 g / m 2 More preferably, 2.0 g / m 2 The fiber sheet preferably has a basis weight of 10.0 g / m from the viewpoint of improving the proton conductivity of the composite membrane. 2 Less than 8.0 g / m 2 More preferably, 7.0 g / m or less 2 It is. Moreover, from the viewpoint of improving electrical properties when used as a composite film, the volatile component content of the fiber sheet of this embodiment is preferably 10 wt % or less, more preferably 5 wt % or less, and even more preferably 3 wt % or less. In order to enhance the affinity between the above-mentioned fiber sheet and the electrolyte membrane, the surface of the porous body may be subjected to a chemical treatment such as sulfonation, which may promote adhesion of the proton-conducting polymer to the porous body.

[0144] A specific example of a method for producing a fiber sheet that can be used as the polyimide-containing porous body in this embodiment is as follows. First, DMAc varnish of polyimide having the structure represented by formula (1) is prepared so that the polyimide is 25% by mass. The prepared varnish is subjected to electrospinning deposition using an electrospinning device with a nozzle needle diameter of 0.2 to 0.5 mm, a length of 20 to 40 mm, a distance between the needle electrode and the collector electrode on which the nanofibers are deposited of 10 to 40 cm, a voltage applied between the electrodes of 30 kV, a flow rate of the varnish of 0.3 mL / h, and a Kapton film as a support placed on the collector electrode, to obtain a fiber sheet. By including a polyimide having a structure represented by formula (1), the solubility in a solvent can be increased, the solid content concentration during spinning can be increased, and a fiber sheet can be obtained with high productivity.

[0145] [Composite membrane] The composite membrane of the present embodiment includes a processed body containing the composition of the present embodiment and an electrolyte membrane having proton conductivity. That is, the composite membrane of the present embodiment can be said to have a configuration in which the electrolyte membrane is reinforced by a processed body containing a polyimide having a structure represented by formula (1), and can exhibit excellent durability and ion conductivity even under high temperature and low humidity conditions. The processed body containing the composition of this embodiment contains a polyimide having a structure represented by formula (1) (hereinafter, also referred to as "polyimide in this embodiment"). Because of this configuration, the composition of this embodiment can suppress thermal expansion even at high temperatures due to the high heat resistance (high glass transition point) of polyimide. In addition, the elastic modulus of polyimide can be maintained even at high temperatures due to the high glass transition point of polyimide. Therefore, a composite film that maintains mechanical strength even at high temperatures can be formed.

[0146] The composite membrane of the present embodiment includes the fiber sheet of the present embodiment and an electrolyte membrane having proton conductivity. That is, the composite membrane of the present embodiment can be said to have a configuration in which the electrolyte membrane is reinforced by the fiber sheet porous body containing the polyimide of the present embodiment, and can exhibit excellent durability and ion conductivity even under high temperature and low humidity conditions. The fiber sheet has fibers deposited two-dimensionally, and is characterized by little constraint in the three-dimensional direction. Therefore, when the polyimide of the present embodiment is used as the core material of the composite membrane as a fiber sheet, the dimensional change of the fiber length in the two-dimensional direction during swelling at the time of humidification is strongly suppressed, while the change in the thickness direction of the fiber sheet is weakly suppressed. By suppressing the dimensional change in the two-dimensional direction, durability against repeated swelling and shrinkage is improved, while the membrane can swell in the thickness direction to hold water, thereby maintaining high proton conductivity. In addition, since the composition of the present embodiment has a high affinity with perfluoro-based proton exchange membranes having acidic groups such as sulfonic acid groups and carboxylic acid groups, the processed body exists in a proton-conductive electrolyte membrane with few voids, and exerts a reinforcing effect as a processed body. In addition, since there are few voids that inhibit proton conduction, proton conductivity can also be exerted well. Therefore, in particular, a composite membrane using the composition of the present embodiment as a processed body exhibits excellent durability and ion conductivity even under high temperature and low humidity conditions. That is, the composition of the present embodiment can be suitably used as a processed body of a composite membrane.

[0147] The processed body of the present embodiment is not particularly limited as long as it contains a polyimide having a structure represented by formula (1), and may be, for example, a porous body, a nanofiber, or any other processed body having various shapes.

[0148] The method for producing a processed body as a porous body is not particularly limited and various known methods can be adopted. Examples of the method for producing a processed body as a porous body include a thermally induced phase separation method and a non-solvent induced phase separation method that use phase separation to produce a porous body. The method for producing the processed body as a nanofiber is not particularly limited, and various known methods can be adopted. Examples of the method for producing the processed body as a nanofiber include a method for producing a nonwoven fabric, such as an electrospinning deposition method (also called an electrospray deposition method), a melt blow method, a spunbond method, and a papermaking method. The mechanical strength of the nonwoven fabric can be increased by subjecting it to heat treatment, press treatment, calendar treatment, plasma treatment, infrared irradiation, ultraviolet irradiation, electron beam irradiation, gamma ray irradiation, etc. In addition, the amount of volatile components in the processed body in this embodiment is preferably 10 wt% or less, more preferably 5 wt% or less, and even more preferably 3 wt% or less, from the viewpoint of electrical properties (particularly electrical properties when applied to a fuel cell). The amount of volatile components can be measured, for example, by the method described in the examples below. In order to enhance the affinity between the porous body and the electrolyte membrane, the surface of the porous body may be subjected to a chemical treatment such as sulfonation, which may promote adhesion of the proton-conducting polymer to the porous body.

[0149] A specific example of a method for producing a fiber sheet, which is one of the processed bodies of this embodiment, is as follows. First, DMAc varnish of polyimide having the structure represented by formula (1) is prepared so that the polyimide content is 25 mass %. The prepared varnish is electrospinned using an electrospinning device with a nozzle needle diameter of 0.2 to 0.5 mm, a length of 20 to 40 mm, a distance between the needle electrode and the collector electrode on which the nanofibers are deposited of 10 to 40 cm, a voltage applied between the electrodes of 30 kV, a flow rate of the varnish of 0.3 mL / h, and a Kapton film as a support placed on the collector electrode, to obtain a fiber sheet.

[0150] A specific example of a method for producing a composite film using the above-mentioned processed body is as follows. First, a Kapton film is used as a support, and a solution of, for example, 10% by mass of perfluorocarbon polymer compound (hereinafter referred to as PFSA) (solvent is a mixture of ethylene glycol, ethanol, water, isopropyl alcohol, etc.) is applied to the PFSA-coated portion so that the wet film thickness is about 130 μm. A fiber sheet is laminated onto the PFSA-coated portion without wrinkles, and after being sufficiently impregnated with the PFSA solution, it is dried at about 70°C for about 30 minutes. After drying, the PFSA solution is again applied onto the laminate of the PFSA and fiber sheet, dried at about 70°C for about 30 minutes, washed with water, and then heat-treated at about 160°C, and peeled off from the Kapton film support to form a composite film. In such a production method, since the polyimide in the present embodiment contains a basic skeleton, it has high affinity with perfluorinated proton exchange membranes having acidic groups such as sulfonic acid groups and carboxylic acid groups, and it is possible to produce a composite membrane that has excellent impregnation and application properties with a PFSA solution and has few voids in the membrane.

[0151] The processed body in this embodiment may contain a polymer other than the polyimide in this embodiment, as long as the function of the processed body is not impaired. Examples of polymers other than polyimide include polyethersulfone, polybenzimidazole, polybenzoxazole, polyamic acid (also called polyimide precursor), polyamide, polyphenylene ether, epoxy resin, acrylic resin, methacrylic resin, polyethylene, polypropylene, and silicone.

[0152] The electrolyte membrane in this embodiment is not particularly limited, and for example, the following A' component can be used as an electrolyte membrane having proton conductivity. The electrolyte membrane can also contain B' to C' components as necessary. The electrolyte membrane in this embodiment is also defined as a membrane prepared from a polymer electrolyte composition containing A' component, and B' and C' components as necessary. Each component contained in the polymer electrolyte composition will be described in detail below.

[0153] (Polymer electrolyte (A' component)) The polymer electrolyte (A' component) is preferably, for example, a perfluorocarbon polymer compound having an ion exchange group, or a hydrocarbon polymer compound having an aromatic ring in the molecule to which an ion exchange group has been introduced, etc. The ion exchange capacity is preferably 0.5 to 3.0 meq / g. Examples of the hydrocarbon polymer compound having an aromatic ring in the molecule include polyphenylene sulfide, polyphenylene ether, polysulfone, polyether sulfone, polyether ether sulfone, polyether ketone, polyether ether ketone, polythioether ether sulfone, polythioether ketone, polythioether ether ketone, polybenzimidazole, polybenzoxazole, polyoxadiazole, polybenzoxazinone, polyxylylene, polyphenylene, polythiophene, polypyrrole, polyaniline, polyacene, polycyanogen, polynaphthyridine, polyphenylene sulfide sulfone, polyphenylene sulfone, polyimide, polyetherimide, polyesterimide, polyamideimide, polyarylate, aromatic polyamide, polystyrene, polyester, and polycarbonate.

[0154] Among them, the above-mentioned hydrocarbon-based polymer compound having an aromatic ring in the molecule is preferably polyphenylene sulfide, polyphenylene ether, polysulfone, polyether sulfone, polyether ether sulfone, polyether ketone, polyether ether ketone, polythioether ether sulfone, polythioether ketone, polythioether ether ketone, polybenzimidazole, polybenzoxazole, polyoxadiazole, polybenzoxazinone, polyxylylene, polyphenylene, polythiophene, polypyrrole, polyaniline, polyacene, polycyanogen, polynaphthyridine, polyphenylene sulfide sulfone, polyphenylene sulfone, polyimide, or polyetherimide from the viewpoint of heat resistance, oxidation resistance, and hydrolysis resistance. Examples of the ion exchange group introduced into the aromatic ring of the above-mentioned hydrocarbon-based polymer compound having an aromatic ring in the molecule include a sulfonic acid group, a sulfonimide group, a sulfonamide group, a carboxylic acid group, and a phosphoric acid group, and the sulfonic acid group is preferable.

[0155] As the polymer electrolyte (component A) used in this embodiment, from the viewpoint of chemical stability, a perfluorocarbon polymer compound having an ion exchange group is suitable. Examples of the perfluorocarbon polymer compound having an ion exchange group include perfluorocarbon sulfonic acid resins, perfluorocarbon carboxylic acid resins, perfluorocarbon sulfonimide resins, perfluorocarbon sulfonamide resins, perfluorocarbon phosphate resins, and amine salts and metal salts of these resins.

[0156] Specific examples of the polymer electrolyte (component A) used in this embodiment include perfluorocarbon polymer compounds having a structural unit represented by formula (2). -[CF2CX 1 X 2 ] a -[CF2-CF((-O-CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d-(CFR 2 ) e -(CF2) f -X 4 )] g - (2)

[0157] During the ceremony, X 1 , X 2 and X 3 are each independently selected from the group consisting of a halogen atom and a perfluoroalkyl group having 1 to 3 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom or a chlorine atom is preferable. X 4 represents COOZ, SO3Z, PO3Z2, or PO3HZ. Z is a hydrogen atom, an alkali metal atom such as a lithium atom, a sodium atom, or a potassium atom; an alkaline earth metal atom such as a calcium atom or a magnesium atom; or NH4, NH3R x1 , NH2R x1 R x2 , N.H.R. x1 R x2 R x3 , N.R. x1 R x2 R x3 R x4 R is an amine selected from the group consisting of x1 , R x2 , R x3 and R x4 are each independently selected from the group consisting of alkyl groups and arene groups. X 4 When is PO3Z2, Z may be the same or different. R x1 , R x2 , R x3 and R x4 The alkyl group in the formula (I) is not particularly limited, but may be any of the following: n H 2n+1 (n is an integer of 1 or more, preferably an integer of 1 to 20, and more preferably an integer of 1 to 10). x1 , R x2, R x3 and R x4 Examples of the alkyl group in x3 and x4 include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, and the like. The arene group is not particularly limited, and examples thereof include a residue obtained by removing one hydrogen atom from the nucleus of an aromatic hydrocarbon (a monocyclic or condensed ring having 6 to 16 carbon atoms). Specifically, a phenyl group, a tolyl group, a naphthyl group, and the like can be mentioned. The alkyl group and the arene group may be substituted. R 1 and R 2 are each independently selected from the group consisting of a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, and a fluorochloroalkyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and a fluorine atom or a chlorine atom is preferable. a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d, e, and f are each independently an integer from 0 to 6 (however, d, e, and f are not simultaneously 0).

[0158] When Z in formula (2) is an alkaline earth metal, for example, two Xs may form a salt with the alkaline earth metal, such as (COO)2Z or (SO3)2Z. 4 may form a salt with the alkaline earth metal.

[0159] Among the perfluorocarbon polymers having an ion exchange group, a perfluorocarbon sulfonic acid polymer represented by formula (3’) or (4’) or a metal salt thereof is more preferable. -[CF2CF2] a -[CF2-CF((-O-CF2-CF(CF3)) b -O-(CF2) h -SO3X)] g - (3’)

[0160] In formula (3’), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, b is an integer from 1 to 3, h is an integer from 1 to 8, and X is a hydrogen atom or an alkali metal atom.

[0161] -[CF2CF2] a -[CF2-CF(-O-(CF2) h -SO3X)] g - (4’)

[0162] In formula (4’), a and g are numbers satisfying 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1, m is an integer from 1 to 8, and X is a hydrogen atom or an alkali metal atom.

[0163] When the ion exchange capacity of the polymer electrolyte (A’ component) in the present embodiment is 3.0 meq / g or less, swelling of the electrolyte membrane tends to be reduced under high temperature and high humidity during fuel cell operation. By reducing the swelling, problems such as a decrease in the strength of the electrolyte membrane, the occurrence of wrinkles and peeling from the electrode, and further a problem of reduced gas barrier properties can also be reduced. Also, when the ion exchange capacity is 0.5 meq / g or more, the power generation ability of the fuel cell equipped with the electrolyte membrane tends to be maintained well. The ion exchange capacity of the polymer electrolyte (A component) is preferably 0.5 to 3.0 meq / g, more preferably 0.65 to 2.0 meq / g, and even more preferably 0.8 to 1.5 meq / g.

[0164] (Compound (B’ component) having a thioether group) As the compound (B component) having a thioether group that can be used in the present embodiment, -(R-S) nIt is a compound containing a chemical structure of - (S is a sulfur atom, R is a hydrocarbon group, and n is an integer of 1 or more), and examples thereof include dialkyl thioethers such as dimethyl thioether, diethyl thioether, dipropyl thioether, methyl ethyl thioether, and methyl butyl thioether, cyclic thioethers such as tetrahydrothiophene and tetrahydroapyran, and aromatic thioethers such as methyl phenyl sulfide, ethyl phenyl sulfide, diphenyl sulfide, and dibenzyl sulfide. These may be used as monomers or as polymers such as polyphenylene sulfide (PPS). From the viewpoint of durability, the compound having a thioether group (component B) is preferably a polymer (oligomer, polymer) in which n is an integer of 10 or more in the above chemical structure, and more preferably a polymer in which n is an integer of 1,000 or more.

[0165] As the compound having a thioether group (component B) used in this embodiment, from the viewpoint of chemical stability, a polyphenylene sulfide resin is suitable. The polyphenylene sulfide resin is a polyphenylene sulfide resin having a paraphenylene sulfide skeleton preferably at 70 mol % or more, more preferably at 90 mol % or more.

[0166] As the B' component, a polyphenylene sulfide having an acidic functional group introduced into the benzene ring can also be suitably used. The acidic functional group to be introduced is preferably a sulfonic acid group, a phosphoric acid group, a carboxylic acid group, a maleic acid group, a maleic anhydride group, a fumaric acid group, an itaconic acid group, an acrylic acid group, or a methacrylic acid group, and more preferably a sulfonic acid group. The method of introducing the acidic functional group is not particularly limited, and is carried out using a general method. For example, the introduction of a sulfonic acid group can be carried out under known conditions using a sulfonating agent such as sulfuric anhydride or fuming sulfuric acid. Specifically, the introduction can be carried out under the conditions described in K. Hu, T. Xu, W. Yang, Y. Fu, Journal of Applied Polymer Science, Vol. 91, or E. Montoneri, Journal of Polymer Science: Part A: Polymer Chemistry, Vol. 27, 3043-3051 (1989). In addition, those in which the introduced acidic functional group is replaced with a metal salt or an amine salt are also preferably used. As the metal salt, alkali metal salts such as sodium salts and potassium salts, and alkaline earth metal salts such as calcium salts are preferred.

[0167] (Compound having an azole ring (component C')) The compound having an azole ring (component C') used in this embodiment is a compound having a five-membered heterocyclic ring structure containing one or more nitrogen atoms in the ring. The five-membered heterocyclic ring may contain atoms such as oxygen and sulfur in addition to nitrogen. Examples of the azole ring include those having two heteroatoms other than carbon atoms such as imidazole (1,3-diazole), oxazole, thiazole, selenazole, pyrazole (1,2-diazole), isoxazole, and isothiazole; those having three heteroatoms such as 1H-1,2,3-triazole (1,2,3-triazole), 1,2,3-oxadiazole (diazoanhydride), and 1,2,3-thiadizole; and those having four heteroatoms such as 1H-1,2,3,4-tetrazole (1,2,3,4-tetrazole), 1,2,3,5-oxatriazole, and 1,2,3,5-thiatriazole. The above-mentioned azole ring may be condensed with an aromatic ring such as a benzene ring. As the compound containing the above-mentioned five-membered heterocyclic structure, from the viewpoint of obtaining heat resistance, it is preferable to use a compound in which a divalent aromatic group such as a p-phenylene group, an m-phenylene group, a naphthalene group, a diphenylene ether group, a diphenylene sulfone group, a biphenylene group, a terphenyl group, or a 2,2-bis(4-carboxyphenylene)hexafluoropropane group is bonded to a five-membered heterocyclic ring.

[0168] As the compound (component C') having an azole ring used in this embodiment, a polyazole compound is preferable from the viewpoint of chemical stability. Examples of polyazole compounds include polymers of polyimidazole compounds, polybenzimidazole compounds, polybenzobisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, polybenzothiazole compounds, etc. Specifically, polybenzimidazole is preferably used as the above-mentioned component C.

[0169] From the viewpoint of chemical stability, the above-mentioned component C' is preferably a polyazole salt. As the polyazole salt, a compound in which at least a part of the polyazole compound is a polyazole metal salt is preferable, and examples thereof include polyazole alkali metal salts and polyazole alkaline earth metal salts. + , Na + , K + , Rb + , Cs + , Fr + As the polyazole salt, a sodium polyazole salt is more preferable. The amount of metal ions is preferably 0.01 to 100 equivalents (0.01 to 100 equivalents) relative to the total equivalent number of nitrogen present in the heterocycle of the polyazole compound, more preferably 0.05 to 50 equivalents, and even more preferably 0.1 to 10 equivalents. The polyazole compound (including the modified polyazole compound described below) and / or polyazole salt may be used alone or in combination of two or more kinds.

[0170] The molecular weight of the C' component is, as a weight average molecular weight measured by GPC, 300 to 500,000 (polystyrene equivalent).

[0171] In this embodiment, the A' component and the C' component may be, for example, ionically bonded to form an acid-base ion complex, or may be covalently bonded. That is, for example, the sulfonic acid group in the A' component and the nitrogen atom contained in each reactive group, such as an imidazole group, an oxazole group, or a thiazole group, in the C' component may form an ionic bond or a covalent bond.

[0172] In this embodiment, the proportion of the A' component in the solid content of the polymer electrolyte composition is preferably 50 to 99.99 mass %, more preferably 55 to 95 mass %, and further preferably 60 to 90 mass %, from the viewpoint of the balance between ion conductivity and durability.

[0173] (Method of manufacturing composite membrane) A method for producing the composite membrane in this embodiment will be described. The composite membrane in this embodiment can be used, for example, as a component of a fuel cell. The production means is not particularly limited, and the processed body and the electrolyte membrane having proton conductivity may be composited by a pressing method, or the electrolyte membrane having proton conductivity may be composited on the processed body by a casting method (coating method). In this case, any suitable casting method may be used, and examples thereof include, but are not limited to, bar coating, spray coating, slit coating, brush coating, etc. In addition, the composition of the present embodiment and an electrolyte component having proton conductivity may be mixed and cast, and then, by phase separation, a composite membrane may be formed, which includes a processed body containing the composition of the present embodiment and an electrolyte membrane having proton conductivity. In addition, the composition of the present embodiment and an electrolyte component having proton conductivity may be mixed and, by melt extrusion, a composite membrane may be formed, which includes a processed body containing the composition of the present embodiment and an electrolyte membrane having proton conductivity. The composite membrane thus obtained is subsequently subjected to a heat treatment as necessary. The heat treatment can improve the crystallinity in the electrolyte membrane having proton conductivity and stabilize the mechanical strength. The heat treatment temperature is preferably 120 to 300°C, more preferably 140 to 250°C, and further preferably 160 to 230°C. A heat treatment temperature of 120°C or higher can improve the crystallinity and thus contribute to improving the mechanical strength. On the other hand, a heat treatment temperature of 300°C or lower is suitable from the viewpoint of maintaining the properties of the composite membrane. The heat treatment time, which depends on the heat treatment temperature, is preferably 5 minutes to 3 hours, and more preferably 10 minutes to 2 hours.

[0174] (Cleaning process) The composite membrane is then optionally subjected to a cleaning treatment using an acid and / or water. Washing with an acid is preferable from the viewpoint of removing metal ions and organic ions ionically bonded to the ion exchange groups in the electrolyte membrane and improving the ion exchange capacity. Therefore, if sufficient ion exchange capacity can be obtained without washing with an acid, washing with an acid is not necessary. Here, examples of acids used for washing with an acid include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, hydrogen peroxide, phosphonic acid, and phosphinic acid; and organic acids such as tartaric acid, oxalic acid, acetic acid, formic acid, trifluoroacetic acid, aspartic acid, aminobenzoic acid, aminoethylphosphonic acid, inosine, glycerin phosphate, diaminobutyric acid, dichloroacetic acid, cysteine, dimethylcysteine, nitroaniline, nitroacetic acid, picric acid, picolinic acid, histidine, bipyridine, pyrazine, proline, maleic acid, methanesulfonic acid, trifluoromethanesulfonic acid, toluenesulfonic acid, and trichloroacetic acid. These acids can be used alone or in combination of two or more. Furthermore, these inorganic and organic acids may be used as a mixture with water, methyl ethyl ketone, acetonitrile, propylene carbonate, nitromethane, dimethyl sulfoxide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, pyridine, methanol, ethanol, acetone, and the like.

[0175] These acids preferably have a pH of 2 or less at 25°C. The washing temperature can be from 0 to 160°C, but if it is too low, the reaction time will be long, and if it is too high, handling will be difficult, which is not preferable. It is also preferable to use an acid-resistant autoclave for pickling at high temperatures. Washing with water is also carried out as necessary, and in particular when washing with acid is carried out, this is carried out for the purpose of removing acid remaining in the film, but even when washing with acid is not carried out, washing can also be carried out for the purpose of removing impurities in the film. The solvent used for washing may be water or various organic solvents having a pH of 1 to 7. When using water for washing, it is preferable to use a sufficient amount of pure water having a conductivity of 0.06 S / cm or less, and washing is preferably carried out sufficiently until the pH of the washing water reaches 6 to 7.

[0176] (Stretching process) In this embodiment, in addition to the above-described production method, transverse uniaxial stretching, simultaneous biaxial stretching, or sequential biaxial stretching may be performed as necessary. Such stretching treatment can improve the mechanical properties of the composite membrane of this embodiment. The stretching is preferably performed at 1.1 to 6.0 times in the transverse (TD) direction and 1.0 to 6.0 times in the longitudinal (MD) direction, more preferably 1.1 to 3.0 times in the transverse direction and 1.0 to 3.0 times in the longitudinal direction, and further preferably 1.1 to 2.0 times in the transverse direction and 1.0 to 2.0 times in the longitudinal direction. The area stretching ratio is preferably 1.1 to 36 times.

[0177] (Reinforcing material) In this embodiment, in addition to the above-described manufacturing method, reinforcement by adding a reinforcing material made of an inorganic material, an organic material, or an organic-inorganic hybrid material (excluding the processed body of this embodiment) or reinforcement by crosslinking can be performed. The reinforcing material may be a fibrous material, a particulate material, or a flaky material. It may also be a continuous support such as a porous membrane, a mesh, or a nonwoven fabric. In this embodiment, the mechanical strength and the dry-wet dimensional change can be easily improved by performing reinforcement by adding a reinforcing material. In particular, the reinforcing effect is high when a fibrous material or the above-mentioned continuous support is used as the reinforcing material. In addition, a layer that is not reinforced and a layer that is reinforced by the above-mentioned method are laminated in a multilayer structure. The reinforcing material may be added or mixed at the same time as melt-kneading, or may be impregnated with a solution or suspension, or may be laminated with the film after the film is formed.

[0178] (Film thickness) In this embodiment, the thickness of the composite membrane is not limited, but is preferably 1 to 500 μm, more preferably 2 to 100 μm, and further preferably 5 to 50 μm. A membrane thickness of 1 μm or more is preferable in that it can reduce inconveniences such as direct reaction between hydrogen and oxygen, and that the membrane is less likely to be damaged even if a pressure difference or strain occurs during handling during fuel cell production or during fuel cell operation. On the other hand, a membrane thickness of 500 μm or less is preferable in that it maintains ion permeability and performance as a solid electrolyte membrane.

[0179] (EW) In this embodiment, the equivalent mass EW of the electrolyte membrane (the dry mass in grams of the proton exchange membrane per equivalent of proton exchange groups) is not limited, but is preferably 333 to 2000, more preferably 400 to 1500, and further preferably 500 to 1200. By using a proton-conducting polymer with a lower EW, that is, a large proton exchange capacity, the polymer exhibits excellent proton conductivity even under high temperature and low humidity conditions, and when used in a fuel cell, a high output can be obtained during operation.

[0180] [Membrane electrode assembly] The membrane electrode assembly of this embodiment includes the composite membrane of this embodiment. That is, the composite membrane of this embodiment can be used as a constituent member of a membrane electrode assembly and a fuel cell together with an electrode catalyst layer described later. A unit in which two types of electrode catalyst layers, an anode and a cathode, are bonded to both sides of an electrolyte membrane is called a membrane electrode assembly (hereinafter sometimes abbreviated as "MEA"). An assembly in which a pair of gas diffusion layers are bonded to the outer sides of the electrode catalyst layers so as to face each other may also be called an MEA. The electrode catalyst layer in this embodiment is used as an anode catalyst layer and / or a cathode catalyst layer.

[0181] (electrode catalyst layer) The electrode catalyst layer in this embodiment is characterized in that it is composed of an electrode catalyst composition containing: composite particles in which electrode catalyst particles are supported on conductive particles; a polymer electrolyte (which may be the same as component A'); and, as necessary, a polymer electrolyte composition containing a compound having a thioether group (component B') and a compound having an azole ring (component C'). An electrode catalyst is a catalyst that easily generates protons by oxidizing fuel (e.g., hydrogen) at the anode, and generates water by reacting the protons and electrons with an oxidant (e.g., oxygen or air) at the cathode. There are no limitations on the type of electrode catalyst, but platinum is preferably used. In order to strengthen the resistance of platinum to impurities such as CO, an electrode catalyst in which ruthenium or the like is added to or alloyed with platinum may be preferably used. The conductive particles are not particularly limited as long as they are conductive, and examples thereof include carbon black such as furnace black, channel black, and acetylene black, activated carbon, graphite, and various metals. The particle diameter of these conductive particles is preferably 10 angstroms to 10 μm, more preferably 50 angstroms to 1 μm, and even more preferably 100 to 5000 angstroms. The particle diameter of the electrode catalyst particles is not limited, but is preferably 10 to 1000 angstroms, more preferably 10 to 500 angstroms, and even more preferably 15 to 100 angstroms. The composite particles preferably have electrocatalyst particles supported at 1 to 99% by mass, more preferably 10 to 90% by mass, and even more preferably 30 to 70% by mass relative to the conductive particles.Specifically, a suitable example is Pt catalyst-supported carbon such as TEC10E40E manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.

[0182] In this embodiment, the content of the composite particles in the electrode catalyst layer is preferably 20 to 95 mass %, more preferably 40 to 90 mass %, even more preferably 50 to 85 mass %, and even more preferably 60 to 80 mass %. In this embodiment, the mass ratio (B' / C') of the B' component to the C' component is preferably (B' / C')=1 / 99 to 99 / 1. From the viewpoint of the balance between chemical stability and durability (dispersibility), it is more preferable that (B' / C')=5 / 95 to 95 / 5, even more preferable that (B' / C')=10 / 90 to 90 / 10, and even more preferable that (B' / C')=20 / 80 to 80 / 20. In the present embodiment, the proportion of the total mass of the B' component and the C' component in the solid content of the polymer electrolyte composition is preferably 0.01 to 50 mass %. From the viewpoint of the balance between ion conductivity and durability (dispersibility), the proportion is more preferably 0.05 to 45 mass %, further preferably 0.1 to 40 mass %, even more preferably 0.2 to 35 mass %, and particularly preferably 0.3 to 30 mass %.

[0183] The amount of the electrode catalyst supported relative to the electrode area is preferably 0.001 to 10 mg / cm in a state where the electrode catalyst layer is formed. 2 , more preferably 0.01 to 5 mg / cm 2 , and more preferably 0.1 to 1 mg / cm 2 It is.

[0184] In this embodiment, the thickness of the electrode catalyst layer is preferably 0.01 to 200 μm, more preferably 0.1 to 100 μm, and further preferably 1 to 50 μm. In this embodiment, the porosity of the electrode catalyst layer is not particularly limited, but is preferably 10 to 90% by volume, more preferably 20 to 80% by volume, and further preferably 30 to 60% by volume.

[0185] The electrode catalyst layer in this embodiment may further contain polytetrafluoroethylene (hereinafter, sometimes abbreviated as "PTFE") to improve water repellency. In this case, the shape of the PTFE is not particularly limited, but it may be any shape as long as it has a fixed shape, and is preferably particulate or fibrous, and these may be used alone or in combination. In this embodiment, when the electrode catalyst layer contains PTFE, the content thereof is preferably 0.001 to 20 mass%, more preferably 0.01 to 10 mass%, and even more preferably 0.1 to 5 mass%, relative to the total mass of the electrode catalyst layer.

[0186] The electrode catalyst layer in this embodiment may further contain a metal oxide to improve hydrophilicity. In this case, the metal oxide is not particularly limited, but is preferably a metal oxide containing at least one selected from the group consisting of Al2O3, B2O3, MgO, SiO2, SnO2, TiO2, V2O5, WO3, Y2O3, ZrO2, Zr2O3, and ZrSiO4. Among them, Al2O3, SiO2, TiO2, and ZrO2 are more preferable, and SiO2 is even more preferable.

[0187] In this embodiment, when the electrode catalyst layer contains a metal oxide, the content is preferably 0.001 to 20 mass%, more preferably 0.01 to 10 mass%, and even more preferably 0.1 to 5 mass% relative to the total mass of the electrode catalyst layer. The form of the metal oxide may be particulate or fibrous, but it is particularly preferable that the metal oxide is amorphous. The term "amorphous" as used herein means that no particulate or fibrous metal oxide is observed when observed with an optical microscope or an electron microscope.

[0188] (Method of manufacturing electrode catalyst layer) The electrode catalyst layer in this embodiment can be produced, for example, by preparing a polymer electrolyte composition which is a solution or suspension in which a polymer electrolyte (which may be the same as the A' component) having an ion exchange capacity of 0.5 to 3.0 meq / g, and, as necessary, a compound having a thioether group (B' component) and a compound having an azole ring (C' component) are dissolved or suspended in one or more protic solvents, the total mass % of the A' component, the B' component, and the C' component in the polymer electrolyte composition is 0.5 to 30 mass %, and the total mass of the B' component and the C' component in the solid content of the polymer electrolyte composition is 0.01 to 50 mass %, and dispersing the above composite particles in this polymer electrolyte composition in an amount of 1 to 100 mass % relative to the polymer electrolyte composition, and applying this to an electrolyte membrane or another substrate such as a PTFE sheet, followed by drying and solidification. In preparing the electrode catalyst composition, the amount of the composite particles dispersed in the polymer electrolyte composition is preferably 5 to 95% by mass, and more preferably 10 to 90% by mass, relative to the polymer electrolyte composition.

[0189] In this embodiment, the electrode catalyst composition can be applied by various generally known methods such as a screen printing method or a spray method. The electrode catalyst composition may be used with the addition of a solvent, if necessary. Examples of solvents that can be used include single or composite solvents such as water, alcohols (ethanol, 2-propanol, ethylene glycol, glycerin, etc.), and fluorocarbons. The amount of such a solvent added is preferably 0.1 to 90% by mass, more preferably 1 to 50% by mass, and even more preferably 5 to 20% by mass, based on the total mass of the electrode catalyst composition. On the other hand, the electrode catalyst layer in this embodiment can also be obtained by applying or immersing and applying the above-mentioned polymer electrolyte composition to a gas diffusion electrode such as ELAT (registered trademark) manufactured by BASF, in which a gas diffusion layer and an electrode catalyst layer are laminated, and then drying and solidifying the composition. Furthermore, after the electrode catalyst layer is produced, it may be immersed in an inorganic acid such as hydrochloric acid. The temperature for the acid treatment is preferably 5 to 90°C, more preferably 10 to 70°C, and further preferably 20 to 50°C.

[0190] [Fuel cell] The fuel cell of this embodiment includes the membrane electrode assembly of this embodiment. Usually, when the anode and cathode of the MEA are bonded to each other via an electronically conductive material located on the outside of the composite membrane, an operable polymer electrolyte fuel cell can be obtained. In this case, a gas diffusion layer can be set on the outer surface of each of the anode catalyst layer and the cathode catalyst layer, if necessary. As the gas diffusion layer, a commercially available carbon cloth or carbon paper can be used. A representative example of the former is carbon cloth E-tek, B-1 manufactured by BASF, and a representative example of the latter is CARBEL (registered trademark, Japan Gore-Tex Co., Ltd., Japan), TGP-H manufactured by Toray Industries, Inc., Japan, and carbon paper 2050 manufactured by SPECTRACORP, USA. Such a polymer electrolyte fuel cell can be produced by various known methods. Methods for producing polymer electrolyte fuel cells are described in detail, for example, in FUEL CELL HANDBOOK (VAN NOSTRAND REINHOLD, AJAPPLEBY et al., ISBN 0-442-31926-6), Chemistry One Point, Fuel Cells (2nd Edition), edited by Taniguchi Masao and Senoo Manabu, Kyoritsu Shuppan (1992), and the like. The electron conductive material used is a composite material with graphite or resin having grooves formed on its surface for the flow of gases such as fuel and oxidant, or a current collector such as a metal plate. If the MEA does not have a gas diffusion layer, a polymer electrolyte fuel cell can be obtained by incorporating the MEA into a single cell casing (e.g., a PEFC single cell manufactured by ElectroChem, Inc., USA) with gas diffusion layers positioned on the outer surfaces of the anode and cathode of the MEA. In order to obtain a high voltage, a fuel cell is operated as a stack cell in which a plurality of unit cells as described above are stacked. In order to manufacture a fuel cell as a stack cell, a plurality of MEAs are manufactured and a stack cell casing (for example, a casing for a stack cell manufactured by Electrochem, Inc., USA) is placed on the stack cell. The stacked fuel cells are then assembled into a PEFC stack. In these stacked fuel cells, current collectors called bipolar plates are used to separate the fuel and oxidant in adjacent cells and to act as electrical connectors between adjacent cells.

[0191] [Fuel cell system] The fuel cell system of this embodiment includes the fuel cell of this embodiment. The fuel cell is operated by supplying hydrogen to one electrode and oxygen or air to the other electrode. The higher the operating temperature of the fuel cell, the higher the catalytic activity, which is preferable. Usually, the fuel cell is operated at 50 to 80°C, where moisture control is easy, but it can also be operated at 80°C to 150°C. That is, the fuel cell system of this embodiment can include each supply system that supplies hydrogen and oxygen or air to the fuel cell, and a control system that adjusts the pressure, flow rate, temperature, etc. The fuel cell system of this embodiment can be used in, but is not limited to, mobile devices such as mobile phones and smartphones, forklifts, scooters, motorcycles, automobiles, stationary fuel cells (cogeneration systems), power plants, robots, ships, aircraft, rockets, drones, etc.

[0192] <<Combination of the First and Second Embodiments>> An electrolyte membrane can be suitably obtained from the composition of the first embodiment. Moreover, from the composition of the second embodiment, a core material for supporting and reinforcing an electrolyte membrane can be suitably obtained. The first embodiment and the second embodiment can be combined. Specifically, in this embodiment, a composite membrane is obtained that includes an electrolyte membrane obtained from the composition of the first embodiment and a fiber sheet obtained from the composition of the second embodiment. EXAMPLES

[0193] The present embodiment will be described in more detail below with reference to examples and comparative examples, but the present embodiment is not limited thereto. The "Example of the First Embodiment" described below is an example corresponding to the above-mentioned first embodiment, and the "Example of the Second Embodiment" described below is an example corresponding to the second embodiment.

[0194] <<Example of the First Embodiment>> The measurement and evaluation methods used in the examples and comparative examples are as follows. (Ion exchange capacity measurement) Approximately 10 to 50 mg of the fluoropolymer electrolyte pellets or electrolyte membrane was immersed in 50 mL of 25°C saturated NaCl aqueous solution and left to stand for 10 minutes while stirring, and then neutralization titration was performed using 0.01N sodium hydroxide aqueous solution with phenolphthalein as an indicator. After neutralization, the resulting Na-type fluoropolymer electrolyte pellets were rinsed with pure water, vacuum dried, and weighed. The equivalent amount of sodium hydroxide required for neutralization was defined as M (mmol), and the mass of the Na-type polymer electrolyte membrane was defined as W (mg), and the ion exchange capacity (meq / g) was calculated from the following formula. Ion exchange capacity = 1000 / ((W / M)-22)

[0195] (Measurement of solids concentration in ethanol solution of component B) The mass of the weighing bottle was precisely weighed and designated as W0. Approximately 10 g of the object to be measured was placed in the weighing bottle, precisely weighed, and designated as W1. This was dried at 250°C and 0.10 MPa or less for 3 hours or more, then cooled in a desiccator containing silica gel, and after reaching room temperature, was precisely weighed without allowing water absorption, and designated as W2. (W2-W0) / (W1-W0) was expressed as a percentage, and the above was measured a total of 5 times, and the average was designated as the solid concentration.

[0196] (molecular weight measurement) The weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC) under the following conditions. As a solvent, N,N-dimethylformamide (Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography) was used, to which 24.8 mol / L lithium bromide monohydrate (Wako Pure Chemical Industries, Ltd., purity 99.5%) and 63.2 mol / L phosphoric acid (Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography) were added before the measurement. A calibration curve for calculating the weight average molecular weight was prepared using standard polystyrene (Tosoh Corporation). Column: TSK-GEL SUPER HM-H Flow rate: 0.5mL / min Column temperature: 40℃ Pump: PU-2080 (JASCO) Detector: RI-2031Plus (RI: differential refractometer, manufactured by JASCO) UV-2075Plus (UV-Vis: Ultraviolet-visible absorption spectrometer, manufactured by JASCO)

[0197] (Crushability evaluation) The samples were pulverized using Nano Jet Pal (registered trademark) JN100 (manufactured by Joko Co., Ltd.) and evaluated according to the following criteria. Note that 1 Pass refers to the number of ejections required for all samples to pass through the pulverization path, and represents the number of ejections obtained by dividing the amount of all samples by the amount ejected in one pass. Here, pulverizability refers to the ease of pulverizing to a desired particle size. ◎: Crushed to an average diameter of 3 μm or less at a pressure of 180 MPa and 20 passes or less. ○: The powder was crushed to an average diameter of 3 μm or less at a pressure of 180 MPa, more than 20 passes and less than 200 passes. △: Crushed to an average diameter of 3 μm or less at a pressure of 250 MPa and 100 passes or less. ×: The powder was crushed to an average diameter of 3 μm or less at a pressure of 250 MPa, more than 100 passes and not more than 200 passes.

[0198] (Particle size distribution measurement) The particle size distribution was measured using a particle size distribution analyzer LA-920 (HORIBA). Ethanol was used as the dispersion medium, and the measurement was performed after applying ultrasonic waves for 3 minutes at a circulation speed of 3. The refractive index of ethanol was 1.36, and that of the resin was 1.65, and the abundance ratio was evaluated on a volume basis. The average diameter indicates the arithmetic average of the particle size distribution, and the mode diameter indicates the particle diameter with the highest occurrence rate. The abundance ratio indicates the abundance ratio of particles present in the specified particle size range on a volume basis.

[0199] (viscosity measurement) The viscosity (cp) at 1 rpm was measured using an E-type rotational viscometer (Toki Sangyo Co., Ltd. TV-20, cone plate type) at a measurement temperature of 25°C.

[0200] (Dispersibility evaluation) The dispersibility of the composition after mixing was evaluated by measuring the particle size distribution. The particle size distribution was measured using a particle size distribution analyzer LA-920 (manufactured by HORIBA). Ethanol was used as the dispersion medium, and the measurement was performed under the condition of a circulation speed of 3. The refractive index of ethanol was 1.36, and the refractive index of the resin was 1.65, and the presence ratio was evaluated on a volume basis, and the evaluation was performed according to the following criteria. The average diameter indicates the arithmetic average of the particle diameter distribution. ◎: The average particle size was 5 μm or less. ◯: The average particle size was greater than 5 μm and less than 10 μm. △: The average particle size was greater than 10 μm and less than 30 μm. ×: The average particle size was greater than 30 μm.

[0201] (Chemical durability evaluation) Chemical durability evaluation in a fuel cell was performed as follows. First, an electrode catalyst layer was prepared as follows. To 1.00 g of Pt-supported carbon (TEC10E40E manufactured by Tanaka Kikinzoku Co., Ltd., Pt 36.4%), 3.31 g of a polymer solution concentrated to 11 mass % of 5 mass % perfluorosulfonic acid polymer solution SS-910 (manufactured by Asahi Kasei E-materials, equivalent weight (EW): 910, solvent composition: ethanol / water = 50 / 50 (mass ratio)) was added, and 3.24 g of ethanol was added, and the mixture was thoroughly mixed with a homogenizer to obtain an electrode ink. This electrode ink was applied onto a PTFE sheet by screen printing. The application amount was 0.15 mg / cm for both the Pt-supported amount and the polymer-supported amount. 2 The coating amount was 0.30 mg / cm for both Pt and polymer loading. 2 After coating, the electrode was dried at room temperature for 1 hour and at 120°C in air for 1 hour to obtain an electrode catalyst layer with a thickness of about 10 μm. 2 The anode catalyst layer was prepared by adding 0.30 mg / cm of Pt and 0.30 mg / cm of polymer. 2 The above was used as the cathode catalyst layer. The anode catalyst layer and cathode catalyst layer obtained in this manner were placed face to face with a polymer electrolyte membrane sandwiched between them, and hot pressed at 160°C with a surface pressure of 0.1 MPa to transfer and bond the anode catalyst layer and cathode catalyst layer to the polymer electrolyte membrane, thereby producing an MEA. Carbon cloth (ELAT (registered trademark) B-1 manufactured by DE NORA NORTH AMERICA) was set as a gas diffusion layer on both sides of this MEA (the outer surfaces of the anode catalyst layer and the cathode catalyst layer) and assembled into an evaluation cell. This evaluation cell was set in a (Toyo Technica fuel cell evaluation system 890CL), the cell was heated to 95°C, and the gas humidification temperature of the anode and cathode was set to 50°C. Hydrogen was flowed at 50cc / min to the anode side, and air was flowed at 50cc / min to the cathode side. In this state, the chemical durability was evaluated by maintaining the current value at 0 in an open circuit. During durability testing, if a pinhole occurs in the electrolyte membrane, a phenomenon called cross leak occurs, in which hydrogen gas leaks to the cathode side. To check the amount of this cross leak, the hydrogen concentration in the exhaust gas on the cathode side was measured using a micro GC (Varian, model number: CP4900), and the test was terminated when the measured value exceeded 1,000 ppm. The time Hr from the start of the test to the end of the test was used to evaluate the durability test, and durability was judged according to the following criteria. ◎: Showed durability of 300 hours or more. ◯: durability of 200 hours or more and less than 300 hours was shown. △: Durability of 100 hours or more but less than 200 hours was shown. ×: durability of less than 100 hours was shown.

[0202] [Example A1] (Preparation of perfluorocarbon polymer solution having ion exchange groups) A precursor pellet of perfluorosulfonic acid resin (ion exchange capacity after hydrolysis and acid treatment: 1.30 meq / g) obtained from tetrafluoroethylene and CF2=CFO(CF2)2-SO2F, which is a precursor polymer of a polymer electrolyte, was prepared. Next, the precursor pellet was contacted with an aqueous solution of potassium hydroxide (15% by mass) and methyl alcohol (50% by mass) at 80°C for 20 hours to carry out hydrolysis treatment. After that, the pellet was immersed in water at 60°C for 5 hours. Next, the pellet after immersion in water was immersed in 2N hydrochloric acid aqueous solution at 60°C for 1 hour, and this treatment was repeated five times, replacing the hydrochloric acid aqueous solution with a new one each time. Then, the pellet after repeated immersion in the hydrochloric acid aqueous solution was washed with ion-exchanged water and dried. As a result, a perfluorocarbon sulfonic acid resin (PFSA) was obtained as a polymer electrolyte. The pellets were placed in a 5L autoclave together with an aqueous ethanol solution (water:ethanol = 50.0 / 50.0 (mass ratio)) and sealed, and the temperature was raised to 160°C while stirring with a blade and held for 5 hours. The autoclave was then naturally cooled to obtain a uniform perfluorocarbon sulfonic acid resin solution with a solid content concentration of 5% by mass. This was concentrated under reduced pressure at 80°C, and then diluted with water and ethanol to prepare a solution of ethanol:water = 60:40 (mass ratio) with a solid content of 15.0% by mass (A-1).

[0203] (Synthesis of Basic Polymers) A 500mL separable flask with a stirring rod, a Dean-Stark tube and a reflux tube were set up, and the atmosphere in the vessel was replaced with nitrogen gas. 188g of N-methylpyrrolidone (hereafter referred to as "NMP"), 8.52g (38.00mmol) of 5-amino-2-(4-aminophenyl)benzimidazole (Tokyo Chemical Industry Co., Ltd., hereafter referred to as "ABI"), 12.41g (40.00mmol) of 4,4'-oxydiphthalic anhydride (Tokyo Chemical Industry Co., Ltd., hereafter referred to as "ODPA"), and 24g of toluene were added, and the mixture was stirred while introducing nitrogen gas into the reaction vessel. Next, the Dean-Stark tube was filled with toluene, and the internal temperature was raised to 160°C in an oil bath, and the mixture was heated to reflux at 160°C for 2 hours to perform imidization. From the weight of water collected in the Dean-Stark tube, it was confirmed that imidization had progressed by more than 90%. The toluene was then removed from the Dean-Stark tube, and the temperature was raised to 180 °C. The reaction was continued for another 4 h, yielding a product of Mw 5.0 × 10 4 The molecular weight of the polymer is shown in Table 1 below. The reaction solution was cooled to room temperature, and 200 g of NMP was added. A 2 L container was prepared separately from the reaction container, and 600 g of Solmix AP-1 (manufactured by Nippon Alcohol Co., Ltd.) was added. The reaction solution was added dropwise while being stirred to obtain a precipitate. Then, filtration was performed, and the precipitate was washed with ethanol. The recovered material was then dried at 100° C. under reduced pressure for 4 hours to obtain a basic polymer.

[0204] (Microparticulation of basic polymer) The basic polymer obtained above was ground using an agate mortar and pestle, and the powder was sieved through a 53 μm mesh screen, and ethanol was added to the powder to adjust the solid content to 8%. The mixture was then pulverized using JN100 (manufactured by Joko Co., Ltd.) at a pressure of 180 MPa for 20 passes to obtain basic polymer fine particle slurry B-1. The particle size distribution of the basic polymer microparticle slurry B-1 was measured to find that the average diameter was 0.24 μm and the mode diameter was 0.14 μm. The average diameter, mode diameter, abundance rate, and grindability of the basic polymer microparticle slurry are shown in Table 2 below.

[0205] (Preparation of Composition) The perfluorocarbon sulfonic acid resin solution (A-1) and the basic polymer microparticle slurry (B-1) were mixed so that the basic polymer was 6 parts by mass per 100 parts by mass of the perfluorocarbon sulfonic acid resin, and the mixture was concentrated using an evaporator and a warm bath at 50° C. The viscosity and dispersibility of the obtained composition are also shown in Table 3 below.

[0206] (film formation) The composition prepared above was applied to a substrate film using an applicator with an adjusted gap so that the final film thickness was 30 μm. The composition was then heated at 120° C. for 30 minutes and then at 170° C. for 20 minutes to obtain a homogeneous electrolyte membrane with a thickness of 30 μm. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.21 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.9. A SEM photograph of the cross section of the electrolyte membrane is shown in FIG.

[0207] (Chemical durability evaluation) The film obtained above was subjected to the above-mentioned chemical durability evaluation, and the results are shown in Table 3 below.

[0208] [Example A2] The composition was prepared in the same manner as in Example A1, except that the amount of the basic polymer B-1 was 3 parts by mass per 100 parts by mass of the perfluorocarbon sulfonic acid resin. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A2. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.26 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.8.

[0209] [Example A3] The same evaluation as in Example A1 was carried out except that in preparing the basic polymer fine particles, JN100 (manufactured by Joko Co., Ltd.) was used, and the basic polymer fine particle slurry B-2 obtained by passing the particles 10 times at a pressure of 180 MPa was used. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A3. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.22 (meq / g). The average particle size of the basic polymer in the membrane was 1.2 μm, with a coefficient of variation of 0.9.

[0210] [Example A4] When preparing basic polymer microparticles, use JN100 (manufactured by JOKOHAMA) and pass 5 times at a pressure of 180 MPa to obtain basic polymer microparticles slurry B-3.Furthermore, when preparing the composition, except that the basic polymer microparticles are adjusted to 7 parts by mass per 100 parts by mass of perfluorocarbon sulfonic acid resin, evaluation is performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A4. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.23 (meq / g). The average particle size of the basic polymer in the membrane was 1.1 μm, with a coefficient of variation of 0.9.

[0211] [Example A5] In the synthesis of the basic polymer, 8.52g (38.00mmol) of ABI and 12.41g (40.00mmol) of ODPA were changed to 8.97g (40.00mmol) of ABI and 11.17g (36.00mmol) of ODPA, and a basic polymer P-2 was obtained. It was confirmed that imidization of the basic polymer P-2 had progressed to 90% or more. Furthermore, the basic polymer microparticle slurry B-4 was obtained by microparticulating in the same manner as in Example A1. In the preparation of the composition, the basic polymer microparticles were adjusted to 5 parts by mass per 100 parts by mass of perfluorocarbon sulfonic acid resin, and the evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A5. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.23 (meq / g). The average particle size of the basic polymer in the membrane was 0.5 μm, and the coefficient of variation was 0.8.

[0212] [Example A6] During the synthesis of the basic polymer, ABI 8.52g (38.00mmol) was changed to ABI 8.07g (36.00mmol), and basic polymer P-3 was obtained. It was confirmed that imidization of basic polymer P-3 was progressed to 90% or more. By microparticulating in the same manner as in Example A1, basic polymer microparticle slurry B-5 was obtained. Other than that, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A6. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.21 (meq / g). The average particle size of the basic polymer in the membrane was 0.3 μm, with a coefficient of variation of 0.7.

[0213] [Example A7] During the synthesis of the basic polymer, ABI 8.52g (38.00mmol) was changed to ABI 8.75g (39.00mmol), and basic polymer P-4 was obtained. It was confirmed that imidization of basic polymer P-4 had progressed to 90% or more. By microparticulating in the same manner as in Example A1, basic polymer microparticle slurry B-6 was obtained. Other than that, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A7. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.20 (meq / g). The average particle size of the basic polymer in the membrane was 0.3 μm, with a coefficient of variation of 0.7.

[0214] [Example A8] During the synthesis of the basic polymer, 12.41 g (40.00 mmol) of ODPA was replaced with 12.89 g (40.99 mmol) of 3,3',4,4' benzophenonetetracarboxylic dianhydride (Tokyo Chemical Industry Co., Ltd.), to obtain a basic polymer P-5. It was confirmed that imidization had progressed to 90% or more for the basic polymer P-5. By microparticulating the particles in the same manner as in Example A1, a basic polymer microparticle slurry B-7 was obtained. Otherwise, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A8. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.21 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.8.

[0215] [Example A9] During the synthesis of the basic polymer, ODPA 12.41g (40.00mmol) was replaced with 4,4'-biphthalic anhydride (Tokyo Chemical Industry Co., Ltd.) 11.77g (40.00mmol) to obtain basic polymer P-6. It was confirmed that imidization had progressed to 90% or more for basic polymer P-6. By microparticulating in the same manner as in Example A1, basic polymer microparticle slurry B-8 was obtained. Otherwise, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A9. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.21 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.7.

[0216] [Example A10] During the synthesis of the basic polymer, 8.52g (38.00mmol) of ABI was replaced with 7.62g (34.00mmol) of ABI and 1.03g (4.00mmol) of 2,2-bis(3-amino-4-hydroxyphenyl)propane (Tokyo Chemical Industry Co., Ltd.), to obtain basic polymer P-7. It was confirmed that imidization had progressed to 90% or more for basic polymer P-7. By microparticulating in the same manner as in Example A1, basic polymer microparticle slurry B-9 was obtained. Otherwise, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A10. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.21 (meq / g). The average particle size of the basic polymer in the membrane was 0.3 μm, with a coefficient of variation of 0.6.

[0217] [Example A11] During the synthesis of the basic polymer, 8.52g (38.00mmol) of ABI was replaced with 7.62g (34.00mmol) of ABI and 0.99g (4.00mmol) of bis(3-aminophenyl)sulfone (Tokyo Chemical Industry Co., Ltd.), to obtain a basic polymer P-8. It was confirmed that imidization had progressed to 90% or more for the basic polymer P-8. By microparticulating the particles in the same manner as in Example A1, a basic polymer microparticle slurry B-10 was obtained. Otherwise, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A11. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.20 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.8.

[0218] [Example A12] During the synthesis of the basic polymer, 8.52g (38.00mmol) of ABI was replaced with 7.62g (34.00mmol) of ABI and 1.34g (4.00mmol) of 2,2-bis(4-aminophenyl)hexafluoropropane (Tokyo Chemical Industry Co., Ltd.), to obtain a basic polymer P-9. It was confirmed that imidization had progressed to 90% or more for the basic polymer P-9. By microparticulating the particles in the same manner as in Example A1, a basic polymer microparticle slurry B-11 was obtained. Otherwise, evaluation was performed in the same manner as in Example A1. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Example A12. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.22 (meq / g). The average particle size of the basic polymer in the membrane was 0.4 μm, with a coefficient of variation of 0.9.

[0219] [Example A13] The evaluation was carried out in the same manner as in Example A1, except that, in the case of microparticulating the basic polymer, the powder was ground using an agate mortar and pestle, sieved through a 53 μm mesh sieve, and then diluted with ethanol to form a slurry, B-12, was used. The electrolyte obtained in Example A13 gave a film with a rough surface. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.22 (meq / g). The average particle size of the basic polymer in the membrane was 7.5 μm, with a coefficient of variation of 0.8.

[0220] [Comparative Example A1] The evaluation was carried out in the same manner as in Example A1, except that the basic polymer was not added. When the composition was visually observed, it was confirmed that the solution was uniformly dissolved and transparent. In other words, it was evaluated that no particles were present in the obtained composition. It should be noted that a homogeneous membrane was also obtained for the electrolyte obtained in Comparative Example A1. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.30 (meq / g).

[0221] [Comparative example A2] Poly[2,2'-(m-phenylene)-5,5'-bibenzimidazole] (Sigma-Aldrich Japan, weight average molecular weight 27,000, hereinafter referred to as "PBI") (P-10) was used as the basic polymer, and microparticulation was performed in the same manner as in Example A1. However, after 20 passes at 180 MPa, there was no change in the average particle size. Furthermore, the pressure was increased to 250 MPa, and the particle size distribution of the slurry was confirmed every 20 passes. After 180 passes, the average diameter became 1.77 μm, so the slurry (B-13) obtained here was collected. A composition was prepared in the same manner as in Example A1 using B-13, and the dispersibility was evaluated. The average particle size became 38 μm, and particle aggregation was observed. This composition was also evaluated in the same manner as in Example A1. In the electrolyte obtained in Comparative Example A2, unevenness of aggregates was observed which could be visually confirmed. The ion exchange capacity of this electrolyte membrane was measured and found to be 1.06 (meq / g).

[0222] [Table 1]

[0223] The basic group concentrations shown in Table 1 are values ​​calculated from the concentration of azole rings in the monomer concentrations when the basic polymers were synthesized.

[0224] [Table 2]

[0225] [Table 3]

[0226] <<Example of the second embodiment>> The measurement and evaluation methods used in the examples and comparative examples are as follows.

[0227] (molecular weight measurement) The weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC) under the following conditions. As a solvent, N,N-dimethylformamide (Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography) was used, to which 24.8 mol / L lithium bromide monohydrate (Wako Pure Chemical Industries, Ltd., purity 99.5%) and 63.2 mol / L phosphoric acid (Wako Pure Chemical Industries, Ltd., for high performance liquid chromatography) were added before the measurement. A calibration curve for calculating the weight average molecular weight was prepared using standard polystyrene (Tosoh Corporation). Column: TSK-GEL SUPER HM-H Flow rate: 0.5mL / min Column temperature: 40℃ Pump: PU-2080 (JASCO) Detector: RI-2031Plus (RI: differential refractometer, manufactured by JASCO) UV-2075Plus (UV-Vis: Ultraviolet-visible absorption spectrometer, manufactured by JASCO)

[0228] (Solubility evaluation) The polyimide solutions obtained in the examples and comparative examples described below were collected in 50 mL glass sample bottles and allowed to stand at room temperature for 10 days, and the solubility was evaluated according to the following criteria. ◯: No precipitate was formed and fluidity was maintained. △: Slight turbidity occurred, but fluidity was maintained. ×: Precipitation occurred or fluidity was lost.

[0229] (Evaluation of volatile components in porous materials) The thermogravimetric analysis (TGA) was performed under the following conditions, and the weight loss rate from 30°C to 350°C was evaluated as the amount of volatile components. Measurement device: SIIEXSTAR6000 (Seiko Instruments) TG / DTA6200 Measurement atmosphere: Nitrogen Flow rate: 100mL / min Measurement temperature range: 30℃~350℃ Heating rate: 10℃ / min

[0230] (Average fiber diameter of porous body) The average fiber diameter of the porous body was evaluated as follows. The surfaces of the porous bodies obtained in the Examples and Comparative Examples described below were observed using a scanning electron microscope (Hitachi High-Technologies Corporation, S-4800) to obtain secondary electron images, and the results were obtained from electron micrographs taken at a magnification of 5000. Here, the "fiber diameter" refers to the length in the direction perpendicular to the length of the fiber, measured based on an electron micrograph of the fiber.

[0231] (Electrolyte impregnation) The impregnation of the porous body with a solution (perfluorocarbon sulfonic acid resin solution) containing a perfluoro polymer compound having an ion exchange group (hereinafter also referred to as "electrolyte") was evaluated as follows. As shown in the examples and comparative examples described later, a porous body was impregnated with a perfluorocarbon sulfonic acid resin solution to prepare a composite membrane. A sheet cut out at an arbitrary position from the obtained composite membrane was embedded in an epoxy adhesive, and the cross section of the sheet was processed using an ultramicrotome. A secondary electron image of the cut-out sheet cross section was observed over a 10 mm area using a scanning electron microscope (Hitachi High-Technologies Corporation, S-4800). The ratio of the area where the electrolyte was not filled and voids existed in the area where the porous body and the electrolyte were composited was evaluated according to the following criteria. ○: Voids were 0 to 3% or less. △: Voids were more than 3% and less than 10%. ×: Voids exceeded 10%.

[0232] (Dimensional change evaluation) The dimensional change of the electrolyte membrane under 120°C and 100% RH was evaluated as follows. A rectangular frame of approximately 15mm x 20mm was drawn on the electrolyte membrane, and the length of each side was measured using a measuring microscope (OLYMPUS STM6). The electrolyte membrane was placed in a highly accelerated life test device (HAST, EHS-211) and exposed to an environment of 120°C and 100% RH for 2 hours, after which the length of the sides of the frame was measured in the same manner. The rate of change in dimensions before and after swelling was calculated for each of the short and long sides of the rectangle, and the average value was evaluated according to the following criteria. ◎: The average dimensional change rate was 15% or less. ◯: The average dimensional change rate was more than 15% and 30% or less. △: The average dimensional change rate was more than 30% and 40% or less. ×: The average dimensional change rate exceeded 40%.

[0233] (Preparation of MEA) The MEA was prepared as follows. First, an electrode catalyst layer was prepared as follows. To 1.00 g of Pt-supported carbon (TEC10E40E, Tanaka Kikinzoku Co., Ltd., Pt 36.4%), 3.31 g of a polymer solution concentrated to 11 mass% of 5 mass% perfluorosulfonic acid polymer solution SS-910 (Asahi Kasei E-materials Co., Ltd., equivalent weight (EW): 910, solvent composition: ethanol / water = 50 / 50 (mass ratio)) was added, and 3.24 g of ethanol was added, and the mixture was thoroughly mixed with a homogenizer to obtain an electrode ink. This electrode ink was applied onto a PTFE sheet by screen printing. The application amount was 0.15 mg / cm for both the Pt-supported amount and the polymer-supported amount. 2 The coating amount was 0.30 mg / cm for both Pt and polymer loading. 2 After coating, the electrode was dried at room temperature for 1 hour and at 120°C in air for 1 hour to obtain an electrode catalyst layer with a thickness of about 10 μm. 2 The anode catalyst layer was prepared by adding 0.30 mg / cm of Pt and 0.30 mg / cm of polymer. 2 The above was used as the cathode catalyst layer. The anode catalyst layer and cathode catalyst layer thus obtained were placed facing each other, and the composite membrane described below was sandwiched between them. The anode catalyst layer and cathode catalyst layer were transferred and bonded to the composite membrane by hot pressing at 160°C and a surface pressure of 0.1 MPa, to produce an MEA.

[0234] (Fuel cell evaluation) Carbon cloth (ELAT (registered trademark) B-1 manufactured by DE NORA NORTH AMERICA) was set as a gas diffusion layer on both sides of the MEA (the outer surface of the anode catalyst layer and the cathode catalyst layer) and assembled into an evaluation cell. This evaluation cell was set in a (Toyo Technica fuel cell evaluation system 890CL), and the cell was heated to 80°C, after which hydrogen gas was flowed at 300cc / min to the anode side and air gas was flowed at 800cc / min to the cathode side, and both the anode and cathode were pressurized at 0.15MPa (absolute pressure). A water bubbling method was used to humidify the gas, and both hydrogen gas and air gas were humidified at 53°C and supplied to the cell, and the current-voltage curve was measured and evaluated according to the following criteria. ○: 1A / cm 2 The voltage at was 0.6 V or higher. ×: 1A / cm 2 The voltage at was less than 0.6V.

[0235] (Evaluation of chemical durability) Carbon cloth (ELAT (registered trademark) B-1 manufactured by DE NORA NORTH AMERICA) was set as a gas diffusion layer on both sides of the MEA (the outer surfaces of the anode catalyst layer and the cathode catalyst layer) and assembled into an evaluation cell. This evaluation cell was set in a fuel cell evaluation system (890CL manufactured by Toyo Corporation), the cell was heated to 95°C, and the gas humidification temperature of the anode and cathode was set to 50°C. Hydrogen was flowed at 50cc / min to the anode side, and air was flowed at 50cc / min to the cathode side. In this state, the chemical durability was evaluated by maintaining the current value at 0 in an open circuit. During durability testing, if a pinhole occurs in the electrolyte membrane, a phenomenon called cross leak occurs, in which hydrogen gas leaks to the cathode side. To check the amount of this cross leak, the hydrogen concentration in the exhaust gas on the cathode side was measured using a micro GC (Varian, model number: CP4900), and the test was terminated when the measured value exceeded 1,000 ppm. The time Hr from the start of the test to the end of the test was used to evaluate the durability test, and durability was judged according to the following criteria. ◎: Showed durability of 200 hours or more. ◯: durability of 100 hours or more but less than 200 hours was exhibited. ×: durability of 50 hours or more but less than 100 hours was shown.

[0236] [Example B1] (Preparation of a solution of perfluorocarbon polymer compounds having ion exchange groups) A precursor pellet of perfluorosulfonic acid resin (ion exchange capacity after hydrolysis and acid treatment: 1.30 meq / g) obtained from tetrafluoroethylene and CF2=CFO(CF2)2-SO2F, which is a precursor polymer of an electrolyte, was prepared. Next, the precursor pellet was contacted with an aqueous solution of potassium hydroxide (15% by mass) and methyl alcohol (50% by mass) at 80°C for 20 hours to carry out hydrolysis treatment. After that, the pellet was immersed in water at 60°C for 5 hours. Next, the pellet after immersion in water was immersed in 2N hydrochloric acid aqueous solution at 60°C for 1 hour, and this treatment was repeated five times, replacing the hydrochloric acid aqueous solution with a new one each time. Then, the pellet after repeated immersion in the hydrochloric acid aqueous solution was washed with ion-exchanged water and dried. As a result, a perfluorocarbon sulfonic acid resin, which is an electrolyte, was obtained. The pellets were placed in a 5L autoclave together with an aqueous ethanol solution (water:ethanol = 50.0 / 50.0 (mass ratio)) and sealed, and the temperature was raised to 160°C while stirring with a blade and held for 5 hours. The autoclave was then naturally cooled to obtain a uniform perfluorocarbon sulfonic acid resin solution with a solid content concentration of 5% by mass. This was concentrated under reduced pressure at 80°C, and then diluted with water and ethanol to prepare a solution of ethanol:water = 60:40 (mass ratio) with a solid content of 15.0% by mass (A-1).

[0237] (Polyimide synthesis) A 500 mL separable flask with a stirring rod, a Dean-Stark tube and a reflux tube were set up, and the atmosphere in the vessel was replaced with nitrogen gas. 114 g of N-methylpyrrolidone (hereafter referred to as "NMP"), 7.69 g (34.30 mmol) of 5-amino-2-(4-aminophenyl)benzimidazole (manufactured by Tokyo Chemical Industry Co., Ltd., hereafter referred to as "ABI"), 8.52 g (34.30 mmol) of bis(3-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd., hereafter referred to as "33DAS"), 21.71 g (70.00 mmol) of 4,4'-oxydiphthalic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd., hereafter referred to as "ODPA"), and 42 g of toluene were added, and the mixture was stirred while introducing nitrogen gas into the reaction vessel. Next, the Dean-Stark tube was filled with toluene, and the internal temperature was raised to 160°C in an oil bath, and the reaction was refluxed at 160°C for 2 hours to carry out imidization. From the weight of water collected in the Dean-Stark tube, it was confirmed that the imidization had progressed to 90% or more. Next, the toluene was removed from the Dean-Stark tube, and the temperature was raised to 180°C, and the reaction was continued for another 4 hours, resulting in a product of Mw6.7×10 4 The polyimide solution P-3 was obtained. This polyimide had the structure represented by the above formula (1). The polyimide solution was a clear solution without any turbidity. The molecular weight and solubility of the polyimide are shown in Table 4 below.

[0238] (Preparation of porous bodies) Using a NANON manufactured by MEC, the conditions were set as follows: spinning distance 200 mm, voltage 20 kV, and discharge rate 1 mL / hr. Electrospinning was performed using a solution obtained by diluting polyimide solution P-3 to an appropriate viscosity, and a fiber thickness of 3.3 g / m 2 A sheet of the above was produced. The obtained sheet was subjected to a heat treatment in an oven under reduced pressure at 260° C. for 30 minutes. The amount of volatile components in the obtained porous body was 3 wt % or less. When the secondary electron image of the heat-treated sheet was observed using a scanning electron microscope (Hitachi High-Technologies Corporation, S-4800), it was found that the sheet had become porous in the form of nanofibers. A SEM photograph of the porous body is shown in FIG.

[0239] (Preparation of composite membrane) The A-1 solution prepared above was applied to a Kapton film using an applicator with an adjusted gap so that the film thickness after drying would be 8 μm, and the porous body prepared in (Preparation of porous body) was impregnated and heated for 30 minutes at 120° C. Furthermore, a second layer was applied using the same applicator, and heated for 30 minutes at 120° C. and then for 20 minutes at 170° C. to prepare a composite film. The electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite membrane region. The cross section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. The SEM photograph of the cross section of the composite membrane is shown in Figure 3. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5.

[0240] [Example B2] In the polymer synthesis, ABI was changed from 7.69 g (34.30 mmol) to 9.23 g (41.16 mmol), and 33DAS was changed from 8.52 g (34.30 mmol) to 6.81 g (27.44 mmol) to obtain polyimide solution P-4, and the evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet produced using polyimide solution P-4 was a nanofiber-like porous body, and the amount of volatile components in the resulting porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5.

[0241] [Example B3] In the polymer synthesis, ABI was changed from 7.69 g (34.30 mmol) to 12.43 g (55.44 mmol), and 33DAS was changed from 8.52 g (34.30 mmol) to 3.44 g (13.86 mmol) to obtain polyimide solution P-5, and the evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution P-5 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5.

[0242] [Example B4] During the polymer synthesis, ABI was changed from 7.69 g (34.30 mmol) to 13.85 g (61.74 mmol), and 33DAS was changed from 8.52 g (34.30 mmol) to 1.70 g (6.86 mmol) to obtain polyimide solution P-6. The evaluation was performed in the same manner as in Example B1. The obtained polyimide solution P-6 was slightly turbid, but maintained its fluidity. This polyimide had a structure represented by the above formula (1). The sheet made from polyimide solution P-6 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5.

[0243] [Example B5] The procedure of Example B1 was repeated except that NMP was replaced with N,N-dimethylacetamide in the polymer synthesis to obtain polyimide solution P-7. This polyimide had the structure represented by the above formula (1). The sheet made from polyimide solution P-7 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5.

[0244] [Example B6] During the polymer synthesis, NMP was changed from 114 g to 155 g, and ODPA was changed from 21.71 g (70.00 mmol) to 22.56 g (70.00 mmol) of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "BTDA") to obtain polyimide solution PI-8. Evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-8 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0245] [Example B7] In the polymer synthesis, the amount of ABI was changed from 7.69 g (34.30 mmol) to 9.23 g (41.16 mmol), and the amount of 33DAS was changed from 8.52 g (34.30 mmol) to 6.81 g (27.44 mmol), to obtain polyimide solution PI-9. The evaluation was performed in the same manner as in Example B6. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-9 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0246] [Example B8] In the polymer synthesis, NMP 114g was changed to 134g, ABI 7.69g (34.30mmol) to 15.38g (68.60mmol), ODPA 21.71g (70.00mmol) was changed to 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "6FDA") 24.88g (56.00mmol) and ODPA 4.34g (14.00mmol), and 33DAS was not used to obtain polyimide solution PI-10. The evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-10 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0247] [Example B9] The nanofiber-like porous body prepared using the polyimide solution PI-10 was evaluated in the same manner as in Example B8, except that the heat treatment conditions were changed from 260°C under reduced pressure for 30 minutes to 240°C under reduced pressure for 30 minutes. The amount of volatile components in the resulting porous body was 4 wt%. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 5. In the fuel cell evaluation, 2 The voltage at this time was 0.6 V or more, but was about 0.02 V lower than that in Example B8.

[0248] [Example B10] In the polymer synthesis, NMP was changed from 134 g to 129 g, 6FDA from 24.88 g (56.00 mmol) to 18.66 g (42.00 mmol), and ODPA from 4.34 g (14.00 mmol) to 8.69 g (28.00 mmol) to obtain polyimide solution PI-11, and the evaluation was performed in the same manner as in Example B8. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-11 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0249] [Example B11] In the polymer synthesis, NMP 114g was changed to 129g, 33DAS 8.52g (34.30mmol) to 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "6FHA") 12.56g (34.30mmol), ODPA 21.71g (70.00mmol) to BTDA 22.56g (70.00mmol) to obtain polyimide solution PI-12, and the evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-12 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0250] [Example B12] In the polymer synthesis, NMP was changed from 129g to 126g, ABI from 7.69g (34.3mmol) to 9.23g (41.16mmol), and 6FHA from 12.56g (34.30mmol) to 10.05g (27.44mmol) to obtain polyimide solution PI-13, and the evaluation was performed in the same manner as in Example B10. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-13 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0251] [Example B13] In the polymer synthesis, NMP was changed from 126g to 123g, ABI from 9.23g (41.16mmol) to 10.77g (48.02mmol), and 6FHA from 10.05g (27.44mmol) to 7.54g (20.58mmol) to obtain polyimide solution PI-14, and the evaluation was performed in the same manner as in Example B11. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-14 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0252] [Example B14] In the polymer synthesis, NMP was changed from 129g to 118g, and 6FHA was changed from 12.56g (34.30mmol) to 8.86g (34.30mmol) of 2,2-bis(3-amino-4-hydroxyphenyl)propane (Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "BPA-DA") to obtain polyimide solution PI-15. Evaluation was performed in the same manner as in Example B1. This polyimide had a structure represented by the above formula (1). The sheet made from the polyimide solution PI-15 was a nanofiber-like porous body, and the amount of volatile components in the obtained porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite region was 8 μm. Using the obtained membrane, an MEA was fabricated, and the fuel cell performance and chemical durability were evaluated. The results are shown in Table 5.

[0253] [Comparative Example B1] During polymer synthesis, ABI was not added, and 8.52 g (34.30 mmol) of 33DAS was changed to 3.41 g (13.72 mmol) of 33DAS and 5.11 g (20.57 mmol) of bis(4-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter referred to as "44DAS") to obtain polyimide solution P-1. Except for this, evaluation was performed in the same manner as in Example B1. The sheet produced using polyimide solution P-1 was a nanofiber-like porous body, and the amount of volatile components in the resulting porous body was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that more than 50% of the composite region was void and not filled with electrolyte. The cross section was observed by SEM, and the total membrane thickness was 30 μm, and the composite membrane region with voids was 18 μm. The SEM photograph of the cross section of the composite membrane is shown in Figure 4. The gap during deposition was adjusted to a final thickness of 20 μm, and an MEA was fabricated using the membrane. Fuel cell evaluation and chemical durability evaluation were performed, and the results are shown in Table 5. In the fuel cell evaluation, the value was lower by 0.05 V or more than in comparison with Examples B1 to B13.

[0254] [Comparative example B2] During polymer synthesis, ABI 7.69g (34.30mmol) was changed to 14.91g (66.50mmol), and polyimide solution P-2 was obtained without adding 33DAS. The evaluation was performed in the same manner as in Example B1. The obtained polyimide solution P-2 showed precipitation, and lost fluidity when left at room temperature for 10 days. For this reason, it was determined that it was difficult to prepare a porous body by electrospinning, and the evaluation of electrolyte impregnation was not performed.

[0255] [Comparative Example B3] The evaluation was carried out in the same manner as in Example B1, except that no porous body was used.

[0256] [Table 4]

[0257] In Table 4, the numerical value of each component indicates the content ratio of the corresponding component in the composition as a charging ratio.

[0258] [Table 5]

[0259] [Example C1] (Preparation of a solution of perfluorocarbon polymer compounds having ion exchange groups) A precursor pellet of perfluorosulfonic acid resin (ion exchange capacity after hydrolysis and acid treatment: 1.30 meq / g) obtained from tetrafluoroethylene and CF2=CFO(CF2)2-SO2F, which is a precursor polymer of an electrolyte, was prepared. Next, the precursor pellet was contacted with an aqueous solution of potassium hydroxide (15% by mass) and methyl alcohol (50% by mass) at 80°C for 20 hours to carry out hydrolysis treatment. After that, the pellet was immersed in water at 60°C for 5 hours. Next, the pellet after immersion in water was immersed in 2N hydrochloric acid aqueous solution at 60°C for 1 hour, and this treatment was repeated five times, replacing the hydrochloric acid aqueous solution with a new one each time. Then, the pellet after repeated immersion in the hydrochloric acid aqueous solution was washed with ion-exchanged water and dried. As a result, a perfluorocarbon sulfonic acid resin, which is an electrolyte, was obtained. The pellets were placed in a 5L autoclave together with an aqueous ethanol solution (water:ethanol = 50.0 / 50.0 (mass ratio)) and sealed, and the temperature was raised to 160°C while stirring with a blade and held for 5 hours. The autoclave was then naturally cooled to obtain a uniform perfluorocarbon sulfonic acid resin solution with a solid content concentration of 5% by mass. This was concentrated under reduced pressure at 80°C, and then diluted with water and ethanol to prepare a solution of ethanol:water = 60:40 (mass ratio) with a solid content of 15.0% by mass (A-1).

[0260] (Polyimide synthesis) A 500mL separable flask with a stirring rod, a Dean-Stark tube and a reflux tube were set up, and the atmosphere in the vessel was replaced with nitrogen gas. 140g of N-methylpyrrolidone (hereinafter referred to as "NMP"), 15.38g (68.60mmol) of 5-amino-2-(4-aminophenyl)benzimidazole (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "ABI"), 31.10g (70.00mmol) of 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "6FDA"), and 36g of toluene were added, and the mixture was stirred while introducing nitrogen gas into the reaction vessel. Next, the Dean-Stark tube was filled with toluene, and the internal temperature was raised to 160°C in an oil bath, and the mixture was heated to reflux at 160°C for 2 hours to perform imidization. From the weight of water collected in the Dean-Stark tube, it was confirmed that the imidization had progressed to 90% or more. Then, the toluene was removed from the Dean-Stark tube, and the reaction was continued for another 4 hours at a temperature of 180 °C. 4 Thus, a polyimide solution P-3 was obtained. The polyimide solution was a clear solution without any turbidity. The values ​​are shown in Table 7 below.

[0261] (Preparation of porous fiber sheet) Using a NANON manufactured by MEC, the conditions were set as follows: spinning distance 200 mm, voltage 20 kV, and discharge rate 1 mL / hr. Electrospinning was performed using a solution obtained by diluting polyimide solution P-3 to an appropriate viscosity, and fibers with an average fiber diameter of 200 nm and a fiber weight of 3.3 g / m were obtained. 2 A sheet of the above was produced. The obtained sheet was heat-treated in an oven under reduced pressure at 260° C. for 30 minutes. The residual volatile component of the obtained porous fiber sheet was 3 wt % or less. When the secondary electron image of the heat-treated sheet was observed using a scanning electron microscope (Hitachi High-Technologies Corporation, S-4800), it was found to have become a nanofiber-like porous body. An SEM image of the porous body is shown in Figure 5.

[0262] (Preparation of composite membrane) The A-1 solution prepared above was applied to a Kapton film using an applicator with the gap adjusted so that the film thickness after drying would be 8 μm, and the porous body prepared above (Preparation of porous fiber sheet) was impregnated and heated for 30 minutes at 120° C. Furthermore, a second layer was applied using the same applicator, and heated for 30 minutes at 120° C. and then for 20 minutes at 170° C. to prepare a composite film. The electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite membrane region. The cross section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. The SEM photograph of the cross section of the composite membrane is shown in Figure 6. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 7.

[0263] [Example C2] During the polymer synthesis, NMP was changed to N,N-dimethylacetamide to obtain a polyimide solution P-4. Except for this, the evaluation was carried out in the same manner as in Example C1. The sheet made from polyimide solution P-4 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the volatile content was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 7.

[0264] [Example C3] During polymer synthesis, 31.10 g (70.00 mmol) of 6FDA was replaced with 24.88 g (56.00 mmol) of 6FDA and 4.34 g (14.00 mmol) of 4,4'-oxydiphthalic anhydride (Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "ODPA") to obtain polyimide solution P-5. Except for this, evaluation was performed in the same manner as in Example C1. The sheet made from polyimide solution P-5 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the volatile content was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 7.

[0265] [Example C4] During the polymer synthesis, 31.10 g (70.00 mmol) of 6FDA was replaced with 18.66 g (42.00 mmol) of 6FDA and 8.69 g (28.00 mmol) of ODPA to obtain polyimide solution P-6. The evaluation was carried out in the same manner as in Example C1. The sheet made from polyimide solution P-6 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the volatile content was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 7.

[0266] [Comparative Example C1] During polymer synthesis, ABI was not added, but 3.41 g (13.72 mmol) of bis(3-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "33DAS") and 5.11 g (20.57 mmol) of bis(4-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "44DAS") were used to obtain polyimide solution P-1. Except for this, evaluation was performed in the same manner as in Example C1. The sheet produced using polyimide solution P-1 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the volatile component was 3 wt% or less. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that more than 50% of the composite region was void and not filled with electrolyte. The cross section was observed by SEM, and the total membrane thickness was 30 μm, and the composite membrane region with voids was 18 μm. The SEM photograph of the cross section of the composite membrane is shown in Figure 7. The gap during film formation was adjusted to a final film thickness of 20 μm, and an MEA was fabricated using the film. Fuel cell evaluation and chemical durability evaluation were performed. The results are shown in Table 7. In the fuel cell evaluation, the value was lower by 0.05 V or more than in comparison with Examples C1 to C5.

[0267] [Comparative Example C2] During polymer synthesis, ABI was changed from 7.69 g (34.30 mmol) to 14.91 g (66.50 mmol), and polyimide solution P-2 was obtained without adding 33DAS. The evaluation was performed in the same manner as in Example C1. The obtained polyimide solution P-2 showed precipitation, and lost fluidity when left at room temperature for 10 days. For this reason, it was determined that it was difficult to prepare a porous fiber sheet by electrospinning, and the evaluation of electrolyte impregnation was not performed. [Comparative Example C3] The evaluation was carried out in the same manner as in Example C1, except that the porous fiber sheet was not used.

[0268] [Table 6]

[0269] In Table 6, the numerical value of each component indicates the content ratio of the corresponding component in the composition as a charge ratio.

[0270] [Table 7]

[0271] [Example D1] (Preparation of a solution of perfluorocarbon polymer compounds having ion exchange groups) A precursor pellet of perfluorosulfonic acid resin (ion exchange capacity after hydrolysis and acid treatment: 1.30 meq / g) obtained from tetrafluoroethylene and CF2=CFO(CF2)2-SO2F, which is a precursor polymer of an electrolyte, was prepared. Next, the precursor pellet was contacted with an aqueous solution of potassium hydroxide (15% by mass) and methyl alcohol (50% by mass) at 80°C for 20 hours to carry out hydrolysis treatment. After that, the pellet was immersed in water at 60°C for 5 hours. Next, the pellet after immersion in water was immersed in 2N hydrochloric acid aqueous solution at 60°C for 1 hour, and this treatment was repeated five times, changing the hydrochloric acid aqueous solution each time. Then, the pellet after repeated immersion in the hydrochloric acid aqueous solution was washed with ion-exchanged water and dried. As a result, a perfluorocarbon sulfonic acid resin, which is an electrolyte, was obtained. The pellets were placed in a 5 L autoclave together with an aqueous ethanol solution (water:ethanol = 50.0 / 50.0 (mass ratio)) and sealed, and the temperature was raised to 160 ° C while stirring with a blade and held for 5 hours. The autoclave was then naturally cooled to obtain a uniform perfluorocarbon sulfonic acid resin solution with a solid content concentration of 5 mass %. This was concentrated under reduced pressure at 80 ° C, and then diluted with water and ethanol to prepare a solution (A-1 solution) with a solid content of 15.0 mass % and an ethanol:water = 60:40 (mass ratio).

[0272] (Polyimide synthesis) A 500mL separable flask with a stirring rod, a Dean-Stark tube and a reflux tube were set up, and the atmosphere in the vessel was replaced with nitrogen gas. 94g of N-methylpyrrolidone (hereafter referred to as "NMP"), 15.38g (68.60mmol) of 5-amino-2-(4-aminophenyl)benzimidazole (Tokyo Chemical Industry Co., Ltd., hereafter referred to as "ABI"), 15.69g (70.00mmol) of 1,2,4,5-cyclohexanetetracarboxylic dianhydride (Tokyo Chemical Industry Co., Ltd., hereafter referred to as "HPMDA"), and 30g of toluene were added, and the mixture was stirred while introducing nitrogen gas into the reaction vessel. Next, the Dean-Stark tube was filled with toluene, and the internal temperature was raised to 160°C in an oil bath, and the mixture was heated to reflux at 160°C for 2 hours to perform imidization. From the weight of water collected in the Dean-Stark tube, it was confirmed that imidization had progressed by more than 90%. The toluene was then removed from the Dean-Stark tube, and the temperature was raised to 180 °C. The reaction was continued for another 4 h, yielding a product of Mw 6.0 × 10 4 Thus, a polyimide solution P-3 was obtained. The polyimide solution was a clear solution without any turbidity. The molecular weight and solubility of the polyimide are shown in Table 9 below.

[0273] (Preparation of porous bodies) Using a NANON manufactured by MEC, the conditions were set as follows: spinning distance 200 mm, voltage 20 kV, and discharge rate 1 mL / hr. Electrospinning was performed using a solution obtained by diluting polyimide solution P-3 to an appropriate viscosity, and fibers with an average fiber diameter of 200 nm and a fiber weight of 3.3 g / m were obtained. 2 A sheet of the above was produced. The obtained sheet was subjected to a heat treatment in an oven at 260°C under reduced pressure for 30 minutes to obtain a porous body. The residual volatile component of the obtained porous body was 3wt% or less. The thickness of the obtained fiber sheet was 10μm. When the secondary electron image of the heat-treated porous body was observed using a scanning electron microscope (Hitachi High-Technologies Corporation, S-4800), it was found to have become a nanofiber-like porous body. An SEM photograph of the porous body is shown in Figure 8.

[0274] (Preparation of composite membrane) The A-1 solution prepared above was applied to a Kapton film using an applicator with the gap adjusted so that the film thickness after drying would be 8 μm, and the porous body obtained in the above (Preparation of porous body) was impregnated with the solution, followed by heating at 120°C for 30 minutes. Furthermore, a second layer was applied using the same applicator and heated at 120°C for 30 minutes and then at 170°C for 20 minutes to prepare a composite film. The electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite membrane region. The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was produced, and the fuel cell evaluation and chemical durability evaluation were carried out, and the results are shown in Table 9. A SEM photograph of the cross section of the composite membrane is shown in FIG.

[0275] [Example D2] During polymer synthesis, NMP was changed to N,N-dimethylacetamide to obtain polyimide solution P-4, and a porous body and a composite membrane were prepared and evaluated in the same manner as in Example D1, except that polyimide solution P-4 was used. The sheet produced using polyimide solution P-4 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the residual volatile component was 3 wt% or less. The thickness of the obtained sheet was 10 μm. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 9.

[0276] [Example D3] During polymer synthesis, 15.69 g (70.00 mmol) of HPMDA was replaced with 12.55 g (56.00 mmol) of HPMDA and 4.34 g (14.00 mmol) of 4,4'-oxydiphthalic dianhydride (Tokyo Chemical Industry Co., Ltd.; hereinafter referred to as "ODPA") to obtain polyimide solution P-5. Except for using polyimide solution P-5, a porous body and a composite membrane were prepared and evaluated in the same manner as in Example D1. The sheet produced using polyimide solution P-5 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the residual volatile component was 3 wt% or less. The thickness of the obtained sheet was 9 μm. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that there were no voids in the composite region.The cross-section was observed by SEM, and the total membrane thickness was 20 μm, and the composite membrane region was 8 μm. Using the obtained membrane, an MEA was fabricated, and a fuel cell evaluation and chemical durability evaluation were carried out. The results are shown in Table 9.

[0277] [Comparative Example D1] During polymer synthesis, ABI was not added, but 3.41 g (13.72 mmol) of bis(3-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "33DAS") and 5.11 g (20.57 mmol) of bis(4-aminophenyl)sulfone (manufactured by Tokyo Chemical Industry Co., Ltd., hereinafter referred to as "44DAS") were used to obtain polyimide solution P-1. Except for using polyimide solution P-1, a porous body and a composite membrane were prepared and evaluated in the same manner as in Example D1. The sheet produced using polyimide solution P-1 was a nanofiber-like porous body. The average fiber diameter of the obtained porous body was 200 nm, and the residual volatile component was 3 wt% or less. The thickness of the obtained sheet was 11 μm. Furthermore, the electrolyte impregnation of the obtained composite membrane was evaluated, and it was confirmed that more than 50% of the composite region was void, and the electrolyte was not filled in. The cross-section was observed by SEM, and the total membrane thickness was 30 μm, and the composite membrane region with voids was 18 μm. The gap during film formation was adjusted to a final film thickness of 20 μm, and an MEA was fabricated using the film. Fuel cell evaluation and chemical durability evaluation were performed. The results are shown in Table 9. In the fuel cell evaluation, the value was lower by 0.05 V or more than in comparison with Examples D1 to D3. An SEM photograph of the cross section of the composite membrane is shown in FIG.

[0278] [Comparative example D2] In the polymer synthesis, ABI 7.69g (34.30mmol) was changed to 14.91g (66.50mmol), and polyimide solution P-2 was obtained without adding 33DAS and 44DAS, and the evaluation was performed in the same manner as in Example D1, except that polyimide solution P-2 was used. The obtained polyimide solution P-2 showed precipitation and lost fluidity when left at room temperature for 10 days. For this reason, it was judged that it was difficult to prepare a porous body by electrospinning, and the evaluation of electrolyte impregnation was not performed.

[0279] [Comparative Example D3] A composite membrane was prepared and evaluated in the same manner as in Example D1, except that no porous body was used in the preparation of the composite membrane.

[0280] [Table 8]

[0281] In Table 8, the numerical value in parentheses for each component indicates the content ratio of the corresponding component in the composition as a charge ratio (calculated from the amount of substance (mol)).

[0282] [Table 9]

[0283] This application is based on Japanese patent applications filed on February 23, 2017 (Patent Application No. 2017-032159), February 24, 2017 (Patent Application No. 2017-033885), August 8, 2017 (Patent Application No. 2017-153592), August 8, 2017 (Patent Application No. 2017-153437), May 17, 2017 (Patent Application No. 2017-094841), and July 7, 2017 (Patent Application No. 2017-134028), the contents of which are incorporated herein by reference.

Claims

1. A fiber sheet comprising a composition including a polyimide (P1) having a structure represented by formula (1) and having an average fiber diameter of 100 nm or more and 1000 nm or less, The polyimide (P1) is (i) a polyimide (P2) represented by formula (7), or (ii) A fiber sheet comprising a polyimide (P3) represented by formula (8). 【Chemistry 1】 (In formula (1), Y represents a tetravalent organic group.) 【Chemistry 2】 (In formula (7), A is a divalent organic group represented by formula (A-1), (A-2), (A-3) or (A-4); 【Chemistry 3】 (In the above formulas (A-1), (A-3) and (A-4), X 1 represents a divalent organic group represented by the following formula (X1-1) or (X1-2): 【Chemistry 4】 In formulas (A-2) and (A-3), L represents a methyl group or a trifluoromethyl group, and in formula (A-4), R represents a hydroxyl group. Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:

30. 【Chemistry 5】 (In formula (8), D represents a tetravalent organic group represented by formula (D1), Y represents a tetravalent organic group different from D, and the ratio of k:l is 20:80 to 70:30.) 【Chemistry 6】 (In formula (D1), X 1 represents a divalent organic group represented by formula (X1-1) or (X1-2); 【Chemistry 7】 Represents.)

2. The fiber sheet according to claim 1 , wherein the polyimide (P2) comprises a polyimide (P2′) having a structure represented by formula (5). 【Chemistry 8】 (In formula (5), Y represents a tetravalent organic group, m and n represent the numbers of repeating units, and the ratio of m:n is 20:80 to 70:30.)

3. The fiber sheet according to claim 1 or 2, wherein the polyimide (P3) includes a polyimide (P3') having a structure represented by formula (6). 【Chemistry 9】 (In formula (6), Y represents a tetravalent organic group different from the tetravalent group represented by formula (Y1) below, k and l represent the numbers of repeating units, and the ratio of k:l is 20:80 to 70:30.) 【Chemistry 10】

4. The fiber sheet according to any one of claims 1 to 3, wherein the Y is a tetravalent organic group having an alicyclic structure.

5. 5. The fiber sheet according to claim 1, wherein the molecular weight distribution of the composition calculated by Mw / Mn is 2.60 or less.

6. 6. The fiber sheet according to claim 1, wherein the fiber sheet exhibits a weight loss of 10% by mass or less at temperatures from 30° C. to 350° C. in a nitrogen atmosphere.

7. A fiber sheet according to any one of claims 1 to 6, an electrolyte having proton conductivity; Equipped with A composite membrane, wherein an electrolyte having proton conductivity is present within the fiber sheet.

8. 8. The composite membrane according to claim 7, wherein the proton-conducting electrolyte is a perfluorocarbon polymer having an ion-exchange group.

9. A membrane electrode assembly comprising the composite membrane according to claim 7 or 8.

10. A fuel cell comprising the membrane electrode assembly according to claim 9.

11. A fuel cell system comprising the fuel cell according to claim 10.

Citation Information

Patent Citations

  • Polyimide fibre containing benzimidazole structure and preparation method thereof

    CN101200822A

  • Polyimide fiber and preparation method thereof

    CN101984157A

  • Polyimide fiber and preparation method thereof

    CN102191581A

  • Method for preparing polyimide fibers by using liquid crystal spinning

    CN102586930A

  • Continuous production method of polyimide fibers

    CN102817096A